Electrode, electrode complex, secondary battery, and method for manufacturing electrode

JP2025025970AActive Publication Date: 2025-02-21CANON KK
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023131271
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21
Estimated Expiration
2043-08-10

AI Technical Summary

Benefits of technology

【0011】 本開示によれば、活物質粒子の膨張収縮を緩和し、二次電池に用いた際に電池出力特性の低下を抑制することができる電極を提供できる。また、本開示は、本開示の電極を含む電極複合体を提供できる。さらに、本開示は、電池出力の低下が抑制された二次電池を提供できる。加えて、本開示は、再現性の高い電極の製造方法を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025025970000001_ABST
    Figure 2025025970000001_ABST
Patent Text Reader

Abstract

To provide an electrode that can alleviate expansion and contraction of active material particles, and can prevent a reduction in battery output when used in a secondary battery.SOLUTION: An electrode is applied to a secondary battery. The electrode includes active material particles, and resin having conductivity. The active material particles each have an inner surface. The resin having conductivity is located in contact with the inner surface.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrode applied to a secondary battery, an electrode composite, a secondary battery, and a method for manufacturing the electrode. [Background technology]

[0002] In general, secondary batteries are composed of electrodes (positive and negative electrodes) and an electrolyte, and are charged and discharged by the movement of ions between the electrodes via the electrolyte. Such secondary batteries are used in a wide range of applications, from small devices such as mobile phones to large devices such as electric vehicles. For this reason, there is a demand for further improvement in the performance of secondary batteries. In recent years, research and development of so-called all-solid-state batteries, which use inorganic solid electrolytes as the electrolyte, has progressed. By replacing the conventional organic electrolyte with a solid electrolyte, all-solid-state batteries are expected to improve the safety and increase the capacity and output of secondary batteries. On the other hand, in the process of ion insertion and removal in the electrode of an all-solid-state battery, the contact between the electrolyte and the active material particles is easily broken due to the expansion and contraction of the active material particles. As a result, in the all-solid-state battery, the insertion and removal of ions such as lithium ions into and from the active material particles is blocked, the resistance of the electrode increases, and the chargeable and dischargeable current, that is, the output characteristics, is greatly reduced. Therefore, a technology is known in which a lithium ion conductive polymer, which is more flexible than the electrolyte particles, is disposed inside the electrode. Patent Document 1 discloses an electrode in which the outer surfaces of active material particles are partially covered with a lithium ion conductive polymer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-373643 A [Patent Document 2] JP 2020-198301 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the present inventors have found that only partially covering the outer surfaces of the active material particles with a polymer is insufficient to improve the diffusibility of lithium ions in the electrode, which is believed to be due to the following reasons. That is, the active material particles in the electrode expand and contract with charging and discharging. Adjacent active material particles also expand and contract in the same manner. Therefore, if the outer surface of the active material particles is only partially covered with a polymer, the diffusion path of lithium ions consisting of the polymer between the active material particles and the electrolyte particles is easily blocked. In addition, in the active material particles of Patent Document 1, the surface of the active material particles is partially covered with the polymer and the electrolyte particles. Therefore, the contact between the polymer and the electrolyte particles is also limited, and the contact is easily blocked by the expansion and contraction of the active material particles. Therefore, the diffusion of lithium ions is easily restricted between the active material particles and the polymer. As a result, even in a solid electrolyte that generally has a higher ionic conductivity than a polymer, the effect of ion diffusion is easily reduced.

[0005] Furthermore, Patent Document 1 discloses mechanical milling and chemical coating treatment as methods for partially coating the surfaces of active material particles, but such treatment methods have difficulty in making the coating area and thickness uniform for each particle and achieving a uniform coating state, and there is also a problem with reproducibility as a manufacturing method for an electrode.

[0006] The present disclosure reduces the expansion and contraction of active material particles, and suppresses a decrease in battery output when used in a secondary battery. The present disclosure provides an electrode that can suppress the deterioration of the battery output. The present disclosure also provides an electrode composite including the electrode of the present disclosure. In addition, the present disclosure provides a secondary battery in which the deterioration of the battery output is suppressed. Furthermore, the present disclosure provides a method for producing an electrode with high reproducibility. [Means for solving the problem]

[0007] The electrode according to one aspect of the present disclosure comprises: An electrode for use in a secondary battery, The electrode includes active material particles and a conductive resin, the active material particles having an inner surface; The conductive resin is located so as to be in contact with the inner surface.

[0008] An electrode composite according to one aspect of the present disclosure includes: An electrode and an electrolyte layer that transfers an active material between the electrode and the electrolyte layer, The electrode is characterized in that it is an electrode according to the present disclosure.

[0009] A secondary battery according to one aspect of the present disclosure includes: A positive electrode and an electrolyte layer that transfers an active material between the positive electrode and the electrolyte layer, The positive electrode is the electrode according to any one of claims 1 to 22, The secondary battery is characterized in including a negative electrode which transfers the active material between the negative electrode and the electrolyte layer.

[0010] A method for producing an electrode according to one aspect of the present disclosure includes: A 1-1 step of preparing an electrode precursor including active material particles and having gaps between the active material particles; A 2-1 step of preparing a filling material to be filled into the electrode precursor; A 3-1 step of filling the filling material from the outside to the inside of the electrode precursor; and (4-1) a step of retaining the filling material filled inside the electrode precursor inside the electrode precursor. Effect of the Invention

[0011] According to the present disclosure, it is possible to provide an electrode that can reduce the expansion and contraction of active material particles and suppress the deterioration of battery output characteristics when used in a secondary battery. The present disclosure also provides an electrode composite including the electrode of the present disclosure. Furthermore, the present disclosure can provide a secondary battery in which the deterioration of battery output is suppressed. In addition, the present disclosure can provide a method for manufacturing an electrode with high reproducibility. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a conceptual diagram showing a method for producing an electrode precursor. [Diagram 2] FIG. 1 is a diagram showing a schematic configuration of a particle arrangement device 1. [Diagram 3] FIG. 2 is a diagram showing a schematic configuration of a filling device. [Figure 4] FIG. 2 is a schematic diagram of a filler being carried on a first substrate. [Diagram 5] FIG. 2 is an enlarged view of the vicinity of the surface of the first substrate. [Figure 6] FIG. 13 is a diagram showing a schematic configuration of a filling device when brush fibers are used as a support material. [Figure 7] FIG. 2 is a diagram illustrating a configuration of a transfer unit. [Figure 8] 13 is an enlarged view of the vicinity of the surface of a second substrate during a filling process using a second filling device. [Figure 9] FIG. 2 is a diagram showing a schematic view of a second substrate after first particles P1 and second particles P2 have been transferred. [Figure 10] FIG. 2 is a diagram showing a schematic configuration of a particle arrangement device 2. [Figure 11] FIG. 2 is a diagram showing a schematic configuration of a laminate forming apparatus. [Figure 12] FIG. 2 is a diagram showing a schematic configuration of a sintering treatment apparatus. [Figure 13] SEM images of laminates and three-dimensional objects at each stage of the electrode manufacturing method. [Figure 14] 1 is a BIB-SEM image of a three-dimensional object according to one embodiment of the present disclosure. [Figure 15] FIG. 1 is an explanatory diagram of a mechanism relating to a three-dimensional object according to one embodiment of the present disclosure. [Figure 16] FIG. 4 is a diagram showing the results of thermogravimetry of a resin substrate. [Figure 17] Figure showing the results of thermogravimetry and mass spectrometry measurements. [Figure 18-1] FIG. 1 shows LCO particles after the third step. [Figure 18-2] FIG. 13 shows the results of STEM-EDX on LCO particles after the third process. [Figure 19] FIG. 1 is an image diagram showing a method for manufacturing an electrode. [Figure 20]FIG. 3 is a schematic diagram showing one embodiment of step 3-1. [Figure 21] FIG. 4 is a diagram showing a charge / discharge curve of a secondary battery. [Figure 22] FIG. 4 is an electron microscope image of a cross section of a positive electrode. [Diagram 23] FIG. 2 is a low-magnification electron microscope image of a cross section of a positive electrode. [Figure 24] FIG. 1 is a schematic diagram illustrating features of the present disclosure. [Diagram 25] FIG. 4 is an electron microscope image of a cross section of a positive electrode. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" expressing a numerical range means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.

[0014] As a result of the study by the present inventors, it was found that it is important to place a conductive resin (polymer) at an appropriate position relative to the active material particles in the electrode. This makes it easier to suppress the decrease in ion diffusion in the electrode while mitigating the expansion and contraction of each active material particle inside the electrode. In the present disclosure, the electrode of the present disclosure is realized by filling the electrode precursor with a polymer and retaining it inside the electrode precursor by the method described below. In the present disclosure, the mitigation of the expansion and contraction of each active material particle is evaluated conveniently using an index called the "cycle characteristic" of the prototype battery, and the ion conductivity is evaluated conveniently using an index called the "rate characteristic" of the prototype battery.

[0015] The electrode of the present disclosure is an electrode applied to a secondary battery. The electrode includes active material particles and a resin having electrical conductivity. By including the active material particles and the resin having electrical conductivity, ions can be transferred between the electrodes via an electrolyte, and the electrode can be used as an electrode.

[0016] The active material particles preferably have an inner surface, and the conductive resin is preferably located so as to be in contact with the inner surface of the active material particles, where the inner surface refers to the surface present on the inside of the active material particles. In this way, the conductive resin contacts the inner surface of the active material particles, and the flexibility of the conductive resin eases the expansion and contraction of the active material particles, while making it easier to suppress the decrease in ion diffusion in the electrode, and thus suppresses the decrease in output characteristics. For example, by performing a sintering process as in the third step described below, the active material particles can have an inner surface within the particles. In addition, for example, by filling a filling material into an electrode precursor as in the 3-1 step described below, the conductive resin can be positioned so as to be in contact with the inner surface of the active material particles. The fact that the active material particles have an inner surface within the particles can be confirmed by the measurement method described below. In addition, the fact that the conductive resin is positioned so as to be in contact with the inner surface of the active material particles can be confirmed by the measurement method described below.

[0017] The inner surface of the active material particle preferably has an inner hole (hereinafter, also referred to as a communicating hole) formed therein, which is connected to the outer surface of the active material particle. By forming such an inner hole, it becomes easier to position the filling material so as to contact the inner surface of the active material particle in the step 3-1 described later. An example of a method for forming such inner pores is a sintering process as in the third step described below. Furthermore, whether or not the inner surface of the active material particle has such inner pores can be confirmed by a measurement method described below.

[0018] In addition, the inner surface of the active material particle is preferably continuous with the outer surface of the active material particle, which makes it easier to position the conductive resin so as to contact the inner surface of the active material particle in the step 3-1 described later. Moreover, examples of active material particles having such an inner surface include active material particles having a core portion and a shell portion. An example of a method for forming such an inner surface is a sintering process as in the third step described below.

[0019] It is preferable that the active material particles have an outer surface, and the conductive resin is disposed in contact with the outer surface of the active material particles so as to connect the active material particles. Here, the outer surface refers to the surface present on the outside of the active material particles. In this way, the conductive resin is arranged in contact with the outer surfaces of the active material particles and connects the active material particles, and the flexibility of the conductive resin makes it easier to suppress the deterioration of ion diffusion in the electrode while mitigating the expansion and contraction of the active material particles, thereby making it possible to suppress the deterioration of output characteristics. For example, by filling the electrode precursor with a filling material as in step 3-1 described below, the conductive resin can be arranged so as to contact the outer surfaces of the active material particles and connect the active material particles. The fact that the conductive resin is in contact with the outer surfaces of the active material particles and arranged so as to connect the active material particles can be confirmed by the measurement method described below.

[0020] The active material particles preferably have protrusions. The shape of the protrusions is not particularly limited, and examples thereof include whiskers, which are whisker-like, and dendrites, which are dendritic. Examples of the protrusions include those protruding from the outer surface. When the active material particles have protrusions in this way, the surface area of ​​the active material particles increases. As a result, when the electrode contains an electrolyte, the contact area with the electrolyte can be increased. The protrusions can be formed, for example, by carrying out a sintering process as in the third step described below. The fact that the active material particles have protrusions can be confirmed by observing the cross section of the electrode described below.

[0021] The active material particles are not particularly limited and known active material particles can be used. For example, a composite oxide containing lithium can be used. Specifically, for example, Li-Co oxide active material particles such as LiCoO2 (lithium cobalt oxide), LiMO2 (M is one element selected from the group consisting of Ni, Mn, and Co), Li-PO4 oxide active material particles, lithium vanadium compounds (Li3V2(PO4)3, LiVOPO4), olivine phosphate compounds (LiMPO4 (M is one or more elements selected from the group consisting of Co, Ni, Mn, Fe, Mg, V, Nb, Ti, Al, and Zr)), and the like can be used. In addition, active material particles that do not contain lithium can be used. Specifically, for example, metal oxides (MnO2, V2O5, etc.) and fluorides (FeF3, VF3, etc.) can be used. When using active material particles that do not contain lithium, metallic lithium containing lithium or a negative electrode active material doped with lithium ions is placed as the negative electrode active material, and it can be used by starting with discharging. In addition, the negative electrode active material particles, such as graphite, Si, and lithium titanate (LTO), are used. It is also possible.

[0022] The present inventors have revealed that, among the above positive electrode active material particles, the use of Li-Co oxide-based active material particles increases the surface area of ​​the positive electrode active material particles, improving the output characteristics of the secondary battery (Patent Document 2). In addition, Li-PO4 oxide-based active material particles are very stable because the covalent bonds between PO are strong and oxygen release is suppressed. For this reason, among the above positive electrode active material particles, it is preferable to include Li-Co oxide-based active material particles and Li-PO4 oxide-based active material particles.

[0023] The active material particles may be a commercially available product, or may be prepared separately as a material. As the Li-Co oxide-based active material particles, for example, Cellseed C-5H (trade name, manufactured by Nippon Chemical Industry Co., Ltd.) (LiCoO2) can be used. As the LiMO2 (M is an element selected from the group consisting of Ni, Mn, and Co), Cellseed NMC (trade name, manufactured by Nippon Chemical Industry Co., Ltd.) (LiNi (1-x-y) Mn x Co y O2) can be used. As the Li-PO4 oxide-based active material particles, Li3V2(PO4)3 (manufactured by Tokyo Chemical Industry Co., Ltd.) or LiFePO4 (manufactured by Toshima Manufacturing Co., Ltd.) can be used. When active material particles having low electronic conductivity such as Li3V2(PO4)3 or LiFePO4 are used, the particle surfaces may be coated with carbon by a general method. The active material particles may be used alone or in combination of two or more kinds.

[0024] The electrode preferably contains at least one selected from the group consisting of a conductive resin, a conductive assistant, and a supporting electrolyte between the active material particles, and more preferably contains a conductive resin and a supporting electrolyte between the active material particles. This improves the diffusibility of lithium ions in the electrode, thereby reducing the electrode resistance. In addition, the actual capacity of the battery can be improved by reducing the number of isolated active material particles that cannot exchange lithium ions in the electrode. The fact that the electrode contains at least one selected from the group consisting of a conductive resin, a conductive assistant, and a supporting electrolyte between the active material particles can be confirmed by the results of element mapping in the cross-sectional observation described below.

[0025] The resin having electrical conductivity is not particularly limited, and any known resin can be used as long as it has electrical conductivity. For example, the resin having electrical conductivity may be a resin having ionic conductivity. Examples of the resin having electrical conductivity include gel electrolytes and dry polymer electrolytes. From the viewpoint of safety, dry polymer electrolytes that do not contain flammable electrolyte are preferred. The conductive resin preferably contains at least one of polyurethane, polyacrylic, and polyether in the main chain structure. In addition, polyether, urethane resin containing polyether, and acrylic resin containing polyether are more preferable, and urethane resin containing polyether is even more preferable. In addition, as the polyether, a copolymer of polyethylene glycol and polypropylene glycol is preferable. The conductive resin preferably contains an ionic functional group such as a cationic structure in its structure in order to have conductivity. The conductive resin preferably contains an anion. Furthermore, the conductive resin may have conductivity by containing a conductive assistant or a supporting electrolyte.

[0026] The ionic group is preferably at least one cationic structure selected from the group consisting of a cationic nitrogen-containing heterocyclic structure and an ammonium cation having a linear or branched structure. The cationic nitrogen-containing heterocyclic structure is not particularly limited, but may be a four-membered ring to an eight-membered ring. Examples of the cationic nitrogen-containing heterocyclic structure include cationic nitrogen-containing aromatic heterocyclic structures such as imidazolium cation, pyridinium cation, pyrazinium cation, pyrimidinium cation, azepinium cation, quinolinium cation, isoquinolinium cation, indolinium cation, quinoxalinium cation, triazolium cation, triazinium cation, and thiazolinium cation; cationic nitrogen-containing aliphatic heterocyclic structures such as pyrrolidinium cation, pyrrolinium cation, imidazolinium cation, imidazolidinium cation, piperazinium cation, azepanium cation, diazepanium cation such as 1,3-diazepanium cation and 1,4-diazepanium cation, azocanium cation, oxazolinium cation, and morpholinium cation. Among them, the cationic nitrogen-containing aromatic heterocyclic structure is preferably at least one selected from the group consisting of imidazolium cation, pyridinium cation, and pyrazinium cation, and more preferably imidazolium cation. The cationic nitrogen-containing aliphatic heterocyclic structure is preferably at least one selected from the group consisting of a pyrrolidinium cation and a piperazinium cation, and more preferably a pyrrolidinium cation.

[0027] Examples of the ammonium cation having a straight-chain or branched structure include primary ammonium cations, secondary ammonium cations, tertiary ammonium cations and quaternary ammonium cations, and among these, quaternary ammonium cations are preferred. The hydrocarbon group of the ammonium cation is not particularly limited, and may be, for example, a hydrocarbon group having 1 to 8 carbon atoms (preferably 1 to 4, more preferably 1 to 2, and even more preferably 1). The ammonium cation having a linear or branched structure may have a structure represented by the following formula (4). The cationic structure may have any substituent such as a hydrocarbon group. For example, the cationic structure preferably includes at least one structure selected from the group consisting of structures represented by the following formulas (1) to (6). Each structure represented by the formulas (1) to (6) will be described below.

[0028] The structure represented by formula (1) will be described below. [ka] In formula (1), R 1 and R 2 represents a hydrocarbon group which forms a five-membered nitrogen-containing aromatic heterocyclic structure together with the nitrogen atom to which each is bonded, Z 1 ~Z 3 each independently represents a structure represented by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) and a hydroxyl group; Z 1 ~Z 3 At least one of the structures represented by the following formula (X) is 1 represents an integer of 0 to 3 (preferably 0 or 1).

[0029] The hydrocarbon group having 1 to 4 carbon atoms is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and even more preferably an alkyl group having 1 carbon atom. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. In addition, the hydrocarbon group may have two or more hydroxyl groups. The structure represented by formula (1) is composed of at least one structure represented by the following formula (X) and two and a nitrogen atom. The nitrogen-containing aromatic heterocyclic structure in formula (1) is preferably an imidazolium cation. The method for incorporating the structure represented by formula (1) into the structure of a conductive resin is not particularly limited. For example, when the conductive resin is a urethane resin, at least one structure represented by formula (1) is incorporated into the structure of the urethane resin by reacting an ionic compound having a structure corresponding to the cation of the five-membered nitrogen-containing aromatic heterocyclic structure represented by formula (1) with an isocyanate compound.

[0030] As the five-membered nitrogen-containing aromatic heterocyclic structure in formula (1), the cationic nitrogen-containing aromatic heterocyclic structures described in the above-mentioned column on cation structures can be used, and among them, imidazolium cations are preferred. Examples of ionic compounds having a structure corresponding to the cation of the five-membered nitrogen-containing aromatic heterocyclic structure in formula (1) include Z 1 ~Z 3 At least one of the above is a divalent hydrocarbon having a hydroxyl group and having a straight chain or a branched chain. As an example of this ionic compound, an ionic compound containing an imidazolium cation is given below.

[0031] 1-methyl-3-hydroxymethylimidazolium cation, 1-methyl-3-(2-hydroxyethyl)imidazolium cation, 1-methyl-3-(3-hydroxypropyl)imidazolium cation, 1-methyl-3-(4-hydroxybutyl)imidazolium cation, 1-ethyl-3-(2-hydroxyethyl)imidazolium cation, 1-n-butyl-3-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(2-hydroxyethyl)imidazolium cation, 1,3-dimethyl-2-(4-hydroxybutyl)imidazolium cation, 1,3-dimethyl-4-(2-hydroxyethyl)imidazolium cation; 1,3-bishydroxymethylimidazolium cation, 1,3-bis(2-hydroxyethyl)imidazolium cation, 2-methyl-1,3-bishydroxymethylimidazolium cation, 2-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-methyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 4-ethyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 2-n-butyl 1,3-bis(2-hydroxyethyl)imidazolium cation, 4-n-butyl-1,3-bis(2-hydroxyethyl)imidazolium cation, 1,3-bis(3-hydroxypropyl)imidazolium cation, 1,3-bis(4-hydroxybutyl)imidazolium cation, 1-methyl-2,3-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,4-bis(2-hydroxyethyl)imidazolium cation, 1-methyl-3,5-bis(2-hydroxyethyl)imidazolium cation; 1,2,3-trishydroxymethylimidazolium cation, 1,2,3-tris(2-hydroxyethyl)imidazolium cation, 1,2,3-tris(3-hydroxypropyl)imidazolium cation, 1,2,3-tris(4-hydroxybutyl)imidazolium cation, 1,3,4-trishydroxymethylimidazolium cation, 1,3,4-tris(2-hydroxyethyl)imidazolium cation, 1,3,4-tris(3-hydroxypropyl)imidazolium cation, 1,3,4-tris(4-hydroxybutyl)imidazolium cation; and their derivatives.

[0032] The structure represented by formula (2) will be described below. [ka] In formula (2), R 3 represents a hydrocarbon group which forms a nitrogen-containing aromatic heterocyclic structure together with the nitrogen atom to which it is bonded; Z 4 and Z 5each independently represents a structure represented by formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) and a hydroxyl group; Z 4 and Z 5 At least one of the structures represented by formula (X) is 2 represents an integer of 0 to 5 (preferably 0 or 1).

[0033] The hydrocarbon group having 1 to 4 carbon atoms is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and even more preferably an alkyl group having 1 carbon atom. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. In addition, the hydrocarbon group may have two or more hydroxyl groups. The structure represented by formula (2) represents a cation of a nitrogen-containing aromatic heterocyclic structure having at least one structure represented by the following formula (X). The nitrogen-containing aromatic heterocyclic structure in formula (2) may be a five-membered to eight-membered ring, and is preferably a five-membered or six-membered ring. The nitrogen-containing aromatic heterocyclic structure in formula (2) is preferably, for example, a pyridinium cation. The method for incorporating the structure represented by formula (2) into the structure of a conductive resin is not particularly limited. For example, when the conductive resin is a urethane resin, at least one structure represented by formula (2) is incorporated into the structure of the urethane resin by reacting an ionic compound having a structure corresponding to the cation of the nitrogen-containing aromatic heterocyclic structure represented by formula (2) with an isocyanate group.

[0034] As the nitrogen-containing aromatic heterocyclic structure in the formula (2), the cationic nitrogen-containing aromatic heterocyclic structures described in the above section on cation structures can be used, and among these, pyridinium cations are preferred. Examples of ionic compounds having a structure corresponding to the cation of the nitrogen-containing aromatic heterocyclic structure in formula (2) include Z 4 and Z 5At least one of the above is a divalent hydrocarbon having a hydroxyl group and having a straight chain or a branched chain. As an example of this ionic compound, an ionic compound containing a pyridinium cation is shown below.

[0035] 1-hydroxymethylpyridinium cation, 1-(2-hydroxyethyl)pyridinium cation, 1-(3-hydroxypropyl)pyridinium cation, 1-(4-hydroxybutyl)pyridinium cation, 2-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-methyl-1-(2-hydroxyethyl)pyridinium cation, 4-methyl-1-(2-hydroxyethyl)pyridinium cation, 3-ethyl-1-(2-hydroxyethyl)pyridinium cation, 3-n-butyl-1-(2-hydroxyethyl)pyridinium cation, 1-methyl-2-hydroxymethylpyridinium cation, 1-methyl-3-hydroxymethylpyridinium cation, 1-methyl-4-hydroxymethylpyridinium cation, 1-methyl-2-(2-hydroxyethyl)pyridinium cation, 1-methyl-3-(2-hydroxyethyl)pyridinium cation, 1-methyl-4-(2-hydroxyethyl)pyridinium cation, 1-ethyl-3-(2- hydroxyethyl)pyridinium cation, 1-n-butyl-3-(2-hydroxyethyl)pyridinium cation, 2-methyl-4-n-butyl-1-(2-hydroxyethyl)pyridinium cation; 1,2-bishydroxymethylpyridinium cation, 1,3-bishydroxymethylpyridinium cation, 1,4-bishydroxymethylpyridinium cation, 1,2-bis(2-hydroxyethyl)pyridinium cation, 1,3-bis(2-hydroxyethyl)pyridinium cation, 1,4-bis(2-hydroxyethyl)pyridinium cation, 1,2-bis(3-hydroxypropyl)pyridinium cation, 1,2-bis(3-hydroxypropyl)pyridinium cation, 1,3-bis(3-hydroxypropyl)pyridinium cation, 1, 4-bis(3-hydroxypropyl)pyridinium cation, 1,2-bis(4-hydroxybutyl)pyridinium cation, 1,3-bis(4-hydroxybutyl)pyridinium cation, 1,4-bis(4-hydroxybutyl)pyridinium cation, 2-methyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 2-ethyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 5-methyl-1,3-bis(2-hydroxyethyl)pyridinium cation, 5-ethyl-1,3-bis(2-hydroxyethyl)pyridinium cation; 1,2,4-trishydroxymethylpyridinium cation, 1,2,4-tris(2-hydroxyethyl)pyridinium cation, 1,2,4-tris(3-hydroxypropyl)pyridinium cation, 1,2,4-tris(4-hydroxybutyl)pyridinium cation, 1,3,5-trishydroxymethylpyridinium cation, 1,3,5-tris(2-hydroxyethyl)pyridinium cation, 1,3,5-tris(3-hydroxypropyl)pyridinium cation, 1,3,5-tris(4-hydroxybutyl)pyridinium cation; and their derivatives.

[0036] The structure represented by formula (3) will be described below. [ka] In formula (3), R 4 and R 5represents a hydrocarbon group which forms a six-membered nitrogen-containing aromatic heterocyclic structure together with the nitrogen atom to which each is bonded, and Z 6 and Z 7 each independently represents a structure represented by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) and a hydroxyl group; Z 6 and Z 7 At least one of the above is a structure represented by the following formula (X), 3 represents an integer of 0 to 4 (preferably 0 to 2).

[0037] The hydrocarbon group having 1 to 4 carbon atoms is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and even more preferably an alkyl group having 1 carbon atom. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. In addition, the hydrocarbon group may have two or more hydroxyl groups. The structure represented by formula (3) represents a cation of a six-membered nitrogen-containing aromatic heterocyclic structure having at least one structure represented by the following formula (X) and two nitrogen atoms. The nitrogen-containing aromatic heterocyclic structure in formula (3) is preferably, for example, a pyrazinium cation. The method for incorporating the structure represented by formula (3) into the structure of a conductive resin is not particularly limited. For example, when the conductive resin is a urethane resin, at least one structure represented by formula (3) is incorporated into the structure of the urethane resin by reacting an ionic compound having a structure corresponding to the cation of the six-membered nitrogen-containing aromatic heterocyclic structure represented by formula (3) with an isocyanate compound.

[0038] As the six-membered nitrogen-containing aromatic heterocyclic structure in formula (3), the cationic nitrogen-containing aromatic heterocyclic structures described in the above-mentioned section on cation structures can be used, and among these, pyrimidinium cations and pyrazinium cations are preferred. Examples of ionic compounds having a structure corresponding to the cation of the six-membered nitrogen-containing aromatic heterocyclic structure in formula (3) include Z 6 and Z 7 At least one of the above is a divalent hydrocarbon having a hydroxyl group and having a straight chain or a branched chain. As an example of this ionic compound, the following ionic compound includes a pyrimidium cation.

[0039] 1,4-bis(2-hydroxyethyl)pyrimidinium cation, 1,5-bis(3-hydroxybutyl)pyrimidinium cation, 1-(4-hydroxybutyl)-4-(2-hydroxyethyl)pyrimidinium cation, 1,4-bis(2-hydroxyethyl)-2-methylpyrimidinium cation; and derivatives thereof.

[0040] The structure represented by formula (4) will be described below. [ka] In formula (4), R 7 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2 carbon atoms); Z 8 ~Z 10 each independently represents a structure represented by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) and a hydroxyl group; Z 8 ~Z 10 At least one of the above has a structure represented by the following formula (X).

[0041] The hydrocarbon group having 1 to 4 carbon atoms is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and even more preferably an alkyl group having 1 carbon atom. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. In addition, the hydrocarbon group may have two or more hydroxyl groups. The structure represented by formula (4) represents an ammonium cation having at least one structure represented by the following formula (X). There is no particular limitation on the method for incorporating the structure represented by formula (4) into the structure of a conductive resin. For example, when the conductive resin is a urethane resin, at least one structure represented by formula (4) is incorporated into the structure of the urethane resin by reacting an ionic compound having a structure corresponding to the ammonium cation represented by formula (4) with an isocyanate compound.

[0042] As the ammonium cation in formula (4), ammonium cations having a linear or branched structure as described in the above-mentioned cation structure column can be used. Among them, quaternary The ammonium cation is preferred. Examples of ionic compounds having a structure corresponding to the ammonium cation in formula (4) include Z 8 ~Z 10 At least one of the above is a divalent hydrocarbon having a hydroxyl group and having a straight chain or a branched chain. As an example of this ionic compound, the following ionic compound containing a quaternary ammonium cation is given.

[0043] 2-hydroxyethyltrimethylammonium cation, 2-hydroxyethyltriethylammonium cation, 4-hydroxybutyltrimethylammonium cation, 4-hydroxybutyl-tri-n-butylammonium cation; Bis(hydroxymethyl)dimethylammonium cation, bis(2-hydroxyethyl)dimethylammonium cation, bis(3-hydroxypropyl)dimethylammonium cation, bis(4-hydroxybutyl)dimethylammonium cation; Tris(hydroxymethyl)methylammonium cation, tris(2-hydroxyethyl)methylammonium cation, tris(3-hydroxypropyl)methylammonium cation, tris(4-hydroxybutyl)methylammonium cation; and their derivatives.

[0044] The structure represented by formula (5) will be described below. [ka] In formula (5), R 8 and R 9 represents a hydrocarbon group which forms a nitrogen-containing aliphatic heterocyclic structure together with the nitrogen atom to which each is bonded, Z 11 ~Z 14 each independently represents a structure represented by the following formula (X), a hydrogen atom, a hydroxyl group, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) and a hydroxyl group; Z 11 ~Z 14 At least one of the above is a structure represented by the following formula (X), 4 represents an integer of 0 to 4 (preferably 0 to 2).

[0045] The hydrocarbon group having 1 to 4 carbon atoms is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and even more preferably an alkyl group having 1 carbon atom. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. In addition, the hydrocarbon group may have two or more hydroxyl groups. The structure represented by formula (5) represents a cation of a nitrogen-containing aliphatic heterocyclic structure having at least one structure represented by the following formula (X) and two nitrogen atoms. The nitrogen-containing aliphatic heterocyclic structure in formula (5) may be a five-membered ring to eight-membered ring, and is preferably a five-membered ring or a six-membered ring. The nitrogen-containing aliphatic heterocyclic structure in formula (5) is preferably, for example, a piperazinium cation. The method for incorporating the structure represented by formula (5) into the structure of a conductive resin is not particularly limited. For example, when the conductive resin is a urethane resin, at least one structure represented by formula (5) is incorporated into the structure of the urethane resin by reacting an ionic compound having a structure corresponding to the cation of the nitrogen-containing aliphatic heterocyclic structure represented by formula (5) with an isocyanate compound.

[0046] As the nitrogen-containing aliphatic heterocyclic structure in the formula (5), the cationic nitrogen-containing aliphatic heterocyclic structures described in the above column for cation structure can be used, and among them, piperazinium cations are preferred. Examples of ionic compounds having a structure corresponding to the nitrogen-containing aliphatic heterocyclic cation in formula (5) include Z 11 ~Z 14 At least one of the above is a divalent hydrocarbon having a hydroxyl group and having a straight chain or a branched chain. As an example of this ionic compound, an ionic compound containing a piperazinium cation is shown below.

[0047] 1,1-bis(2-hydroxyethyl)piperazinium cation, 1,1,4-tris(2-hydroxyethyl)piperazinium cation, 1,4-bis(3-hydroxypropyl)-1-ethylpiperazinium cation, 1,4-bis(2-hydroxyethyl)-1,3-diethylpiperazinium cation; and derivatives thereof.

[0048] The structure represented by formula (6) will be described below. [ka] In formula (6), R 9 represents a hydrocarbon group which forms a nitrogen-containing aliphatic heterocyclic structure together with the nitrogen atom to which it is bonded, and Z 15 ~Z 17 each independently represents a structure represented by formula (X), a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1), or a hydrocarbon group having 1 to 4 carbon atoms (preferably 1 to 2, more preferably 1) and a hydroxyl group; Z15 ~Z 17 At least one of the above is a structure represented by the following formula (X), 5 represents an integer of 0 to 4 (preferably 0 or 1).

[0049] The hydrocarbon group having 1 to 4 carbon atoms is preferably an alkyl group having 1 to 4 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and even more preferably an alkyl group having 1 carbon atom. The hydrocarbon group having 1 to 4 carbon atoms and a hydroxyl group is preferably a hydroxyalkyl group having 1 to 4 carbon atoms, more preferably a hydroxyalkyl group having 1 to 2 carbon atoms, and even more preferably a hydroxyalkyl group having 1 carbon atom. In addition, the hydrocarbon group may have two or more hydroxyl groups. The structure represented by formula (6) represents a cation of a nitrogen-containing aliphatic heterocyclic structure having at least one structure represented by the following formula (X). The nitrogen-containing aliphatic heterocyclic structure in formula (6) may be a five-membered to eight-membered ring, and is preferably a five-membered or six-membered ring. The nitrogen-containing aliphatic heterocyclic structure in formula (6) is preferably, for example, a pyrrolidinium cation. The method for incorporating the structure represented by formula (6) into the structure of a conductive resin is not particularly limited. For example, when the conductive resin is a urethane resin, at least one structure represented by formula (6) is incorporated into the structure of the urethane resin by reacting an ionic compound having a structure corresponding to the cation of the nitrogen-containing aliphatic heterocyclic structure represented by formula (6) with an isocyanate group.

[0050] As the nitrogen-containing aliphatic heterocyclic structure in the formula (6), the cationic nitrogen-containing aliphatic heterocyclic structures described in the above column for the cation structure can be used, and among them, a pyrrolidinium cation is preferred. Examples of ionic compounds having a structure corresponding to the nitrogen-containing aliphatic heterocyclic cation in formula (6) include Z 15 ~Z 17 At least one of the above is a divalent hydrocarbon having a hydroxyl group and a straight chain or a branched chain. Examples of ionic compounds containing a pyrrolidinium cation include the following.

[0051] 1-methyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-ethyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-butyl-1,2-bis(2-hydroxyethyl)pyrrolidinium cation, 1-methyl-1,2-bis(4-hydroxybutyl)pyrrolidinium cation; and derivatives thereof.

[0052] The structure represented by formula (X) will be described below. [ka] In formula (X), R 10 represents a divalent hydrocarbon group having a straight chain or a branched chain, the symbol "*" represents a bond to a nitrogen atom in formulas (1) to (6) or a bond to a carbon atom in the nitrogen-containing heterocyclic structure in formulas (1) to (3) and formulas (5) to (6), and the symbol "**" represents a bond to a carbon atom in a polymer chain constituting a urethane resin having a cationic structure. R 10 is preferably a linear or branched alkylene group having 1 to 8 carbon atoms (preferably 1 to 4, more preferably 1 to 2). 10 may have an optional substituent such as a hydroxyl group.

[0053] The structure represented by formula (X) may be, for example, a structure formed by reacting an ionic compound having a structure corresponding to the cation of the structure represented by formula (1) to formula (6) with an isocyanate compound, when the conductive resin is a urethane resin. The isocyanate compound is preferably a urethane prepolymer obtained by reacting a polyol such as polyether polyol with an isocyanate compound. For example, polymeric MDI can be used as the isocyanate compound.

[0054] Among the structures represented by formulae (1) to (6), when the cationic structure contains the structure represented by formula (1) or the structure represented by formula (2), the cationic structure has high stability and a high dissociation rate with the anion, which is the counter ion. Therefore, when a lithium salt is contained as a supporting electrolyte, it is preferable because it is easy to generate an interaction with the anion of the lithium salt, promotes the dissociation of the lithium salt, and tends to improve the ionic conductivity.

[0055] When the conductive resin is a urethane resin, the urethane resin preferably has a first urethane bond and a second urethane bond, and further contains a structure represented by formula (7) and a structure represented by formula (8) between the first urethane bond and the second urethane bond. By containing these structures in the urethane resin, the crystallinity of the polymer main chain is suppressed even if the molecular weight between the crosslinking points is large, and the inhibition of ion movement, particularly at low temperatures, is more easily suppressed. Therefore, the ion conductivity and rate characteristics are more likely to be improved. The method for producing such a urethane resin is not particularly limited, but for example, it can be produced by using a polyethylene glycol-propylene glycol copolymer as a polyol and reacting it with an isocyanate compound. It can also be produced by reacting a urethane prepolymer obtained by reacting a polyethylene glycol-propylene glycol copolymer with an isocyanate compound as the isocyanate compound with a polyol. [ka] [ka]

[0056] It is more preferable that the urethane resin contains a structure represented by the following formula (9). By containing the structure represented by the following formula (9), the crystallinity of the polymer main chain is suppressed, and the inhibition of lithium ion migration, particularly at low temperatures, is more easily suppressed. Therefore, the ion conductivity and rate characteristics are easily improved. [ka] In formula (9), m and n are the average number of moles added, each independently being a natural number of 1 or more and satisfying n≦m≦9n. m is preferably 1-110, and more preferably 34-102. n is preferably 1-55, and more preferably 5-43. The structure represented by formula (9) can be obtained, for example, by using a polyether polyol obtained by ring-opening polymerization of ethylene oxide and propylene oxide. In addition, the arrangement of the ethylene oxide structure represented by (-CH2-CH2-O-) and the propylene oxide structure represented by (-CH2-CH(CH3)-O-) in the formula (9) may be a block copolymer or a random copolymer. The random copolymer is preferable.

[0057] The structure of the resin can be identified by using known analytical techniques such as pyrolysis GC / MS, TF-IR, and NMR, either alone or in combination. The conductive resin in contact with the inner surface of the active material particles or the conductive resin in contact with the outer surface of the active material particles can be identified by using known methods capable of mapping the composition, interatomic bonds, crystal structure, etc., either in place of or in addition to the above-mentioned methods. For example, viscoelasticity mapping with cross-sectional SPM, element mapping by TOF-SIMS, carbon-carbon bond mapping by FT-IR or Raman, structural mapping of soft tissue by soft X-ray microscope, etc., can be used. For the soft X-ray microscope, an inspection device attached to a synchrotron radiation facility such as SPring-8 can be used.

[0058] (anion structure) Examples of anions that the conductive resin preferably contains include fluoroalkylsulfonylimide anions, fluorosulfonylimide anions, fluoroalkylsulfonate anions, fluorosulfonate anions, fluoroalkylcarboxylate anions, fluoroalkylmethide anions, fluoroborate anions, fluorophosphate anions, dicyanamide anions, thiocyanate anions, and bisoxalatoborate anions. Examples of the anion include the perchlorate anion and derivatives thereof.

[0059] Specific examples of the fluoroalkylsulfonylimide anion include fluoroalkylsulfonylimide anions having a fluoroalkyl group having 1 to 6 carbon atoms, such as the bis(trifluoromethanesulfonyl)imide anion, bis(pentafluoroethanesulfonyl)imide anion, bis(heptafluoropropanesulfonyl)imide anion, bis(nonafluorobutanesulfonyl)imide anion, bis(dodecafluoropentanesulfonyl)imide anion, and bis(perfluorohexanesulfonyl)imide anion, and cyclic fluoroalkylsulfonylimide anions such as N,N-hexafluoropropane-1,3-disulfonylimide.

[0060] A specific example of the fluorosulfonylimide anion is a bis(fluorosulfonyl)imide anion. Specific examples of the fluoroalkylsulfonate anion include a trifluoromethanesulfonate anion, a fluoromethanesulfonate anion, a perfluoroethanesulfonate anion, a perfluoropropanesulfonate anion, a perfluorobutanesulfonate anion, a perfluoropentanesulfonate anion, a perfluorohexanesulfonate anion, and a perfluorooctanesulfonate anion. Specific examples of the fluoroalkyl carboxylate anion include a trifluoroacetate anion, a perfluoropropionate anion, a perfluorobutyrate anion, a perfluorovalerate anion, and a perfluorocaproate anion. Specific examples of the fluoroalkyl methide anion include fluorinated alkylsulfonyl methide anions such as tris(trifluoromethanesulfonyl)methide anion, tris(perfluoroethanesulfonyl)methide anion, tris(perfluoropropanesulfonyl)methide anion, tris(perfluorobutanesulfonyl)methide anion, tris(perfluoropentanesulfonyl)methide anion, tris(perfluorohexanesulfonyl)methide anion, and tris(perfluorooctanesulfonyl)methide anion.

[0061] A specific example of the fluoroborate anion is a tetrafluoroborate anion. A specific example of the fluorophosphate anion is hexafluorophosphate anion.

[0062] Among these anions, at least one selected from the group consisting of a fluoroalkylsulfonylimide anion, a fluorosulfonylimide anion, a fluoroborate anion, a dicyanamide anion, and a thiocyanate anion is particularly preferred because it reduces the decrease in electrical conductivity in a low-temperature environment.

[0063] The conductive resin preferably has a higher flexibility than the active material particles. When the conductive resin has a higher flexibility than the active material particles, the shape of the resin is easily changed according to the expansion and contraction of the active material particles accompanying charging and discharging. As a result, it is easy to suppress the decrease in ionic conductivity and electronic conductivity. The fact that the conductive resin has a higher flexibility than the active material particles can be confirmed by measuring the Young's modulus with a commercially available device such as a nanoindenter.

[0064] The conductive assistant is not particularly limited, and examples thereof include graphite such as natural graphite and artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon fluoride powder, conductive fibers such as carbon fibers, carbon nanotubes, and metal fibers, metal powders such as gold, platinum, silver, and aluminum, conductive whiskers such as zinc oxide, conductive metal oxides such as titanium oxide, phenylene oxide, and the like. For example, an organic conductive material such as a dielectric material may be used.

[0065] The supporting electrolyte is not particularly limited, and for example, a conductive resin can be used as an organic electrolyte, and may contain an inorganic electrolyte such as a lithium salt. Also, ion-conductive solids that are usually used in all-solid-state batteries can be used. For example, Li-B oxide-based solid electrolyte particles, Li-Yb oxide-based solid electrolyte particles, Nasicon-type solid electrolyte particles (LiAlTi(PO4)3, LiAlGe(PO4)3, etc.), Li-PO-based solid electrolyte particles (Li3PO4, LiPON (particles in which part of O in Li3PO4 is replaced with N), etc.) can be mentioned. Among the above solid electrolyte particles, Li-B oxide-based solid electrolyte particles and Li-Yb oxide-based solid electrolyte particles can be sintered at a relatively low temperature (700°C or less), so that the reaction with the positive electrode active material particles during sintering can be suppressed and ion conductivity can be maintained. For this reason, among the above solid electrolyte particles, it is preferable to include Li-B oxide-based solid electrolyte particles and Li-Yb oxide-based solid electrolyte particles.

[0066] The supporting electrolyte is more preferably a lithium salt, such as at least one selected from the group consisting of LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiAsF6, lower aliphatic lithium carboxylate, LiCl, LiBr, LiI, lithium chloroborane, lithium tetraphenylborate, LiN(CF3SO3)3, and LiN(C2F5SO2)2. Among these, at least one selected from the group consisting of LiN(CF3SO3)3, LiN(C2F5SO2)2 and LiClO4 is preferred. These lithium salts have high chemical stability with respect to lithium-based active materials, and are unlikely to form an insulating coating at the negative electrode interface due to decomposition of the lithium salt. Therefore, the resistance at the negative electrode interface is unlikely to fluctuate. The lithium salts can be used alone or in combination of two or more.

[0067] The content of the supporting electrolyte is preferably 0.8 to 40.0 parts by mass, more preferably 5.0 to 40.0 parts by mass, further preferably 5.0 to 15.0 parts by mass, and particularly preferably 5.0 to 10.0 parts by mass, relative to 100 parts by mass of the conductive resin. When the content of the supporting electrolyte is within this range, it is easily compatible with the conductive resin, does not precipitate even at low temperatures, and high ionic conductivity can be obtained. The type and content of the indicator electrolyte contained in the conductive resin can be measured by solvent extraction and then LC-MS or the like.

[0068] The solid electrolyte particles to be used may be commercially available products, or may be separately prepared as a material. As the Li-B oxide-based solid electrolyte particles, for example, Li3BO3 (manufactured by Toshima Manufacturing Co., Ltd.) or particles in which part of O in Li3BO3 is replaced with C can be used. As the Li-Yb oxide-based solid electrolyte particles, for example, Li 5.9 Yb 0.81 La 0.09 Zr 0.1 (BO3)3, etc. can be used.

[0069] In the case of an electrode containing an inorganic electrolyte between active material particles, it is preferable that the region containing the conductive resin overlaps the region containing the inorganic electrolyte between the active material particles. In this way, the region containing the conductive resin overlaps the region containing the inorganic electrolyte between the active material particles, which is also called the conductive resin and the inorganic electrolyte being coexisting unevenly. It is more preferable that the region containing the conductive resin includes a region containing the inorganic electrolyte. The above-mentioned relationship between the conductive resin and the inorganic electrolyte has the effect of reducing the interface resistance between the inorganic electrolyte particles. Generally, the solid electrolyte (bulk) has better ionic conductivity than the conductive resin, but the solid electrolyte This tends to cause a decrease in conductivity due to the interface resistance between the solid electrolyte particles. By overlapping the conductive resin with the region containing the solid electrolyte particles, it becomes easier to realize an electrode with low resistance without significantly decreasing the high ionic conductivity of the solid electrolyte (bulk). In addition, the above relationship can be confirmed by the results of element mapping in the cross-sectional observation described below.

[0070] <Method of manufacturing electrode precursor> An example of a method for producing an electrode precursor will be described in detail below with reference to the drawings. Hereinafter, the electrode precursor can be a positive electrode precursor by using positive electrode active material particles as the active material particles, for example. Also, the electrode precursor can be a negative electrode precursor by using negative electrode active material particles as the active material particles.

[0071] The method for producing an electrode precursor according to the present disclosure preferably includes the following four steps (step 1, step 2, step 3, and step 4): Figure 1 is a conceptual diagram showing the method for producing an electrode precursor. (1) A first step (S101 in FIG. 1) of forming a particle layer including active material particles and electrolyte particles on a resin substrate having an adhesive portion (2) A second step (S102 in FIG. 1) of forming a laminate by laminating a plurality of resin substrates (hereinafter also referred to as substrates) on which the particle layer is formed. (3) A third step (S103 in FIG. 1) of removing the resin substrate from the laminate and forming a three-dimensional object containing active material particles and electrolyte particles. (4) A fourth step of post-processing the three-dimensional object (S104 in FIG. 1 ).

[0072] (1st step) The first step is a step of forming a particle layer including active material particles and electrolyte particles on a resin substrate having an adhesive portion. In the first step, a particle arrangement device is used to arrange particles on the resin substrate to form a particle layer. Hereinafter, the particle arrangement device 1 and particle arrangement device 2 that can be used will be described in order.

[0073] [Particle placement device 1] 2 is a diagram illustrating a schematic configuration of the particle arrangement device 1. Hereinafter, the first particles P1 refer to the above-mentioned active material particles, and the second particles P2 refer to the above-mentioned electrolyte particles. The particle arrangement device 1 has a first storage container 21a that stores and supplies the first base material 11a, a first belt device 22a that transports the first base material 11a, and a pattern forming device 23 that forms a concave-convex pattern on the first base material 11a. The particle arrangement device 1 has a first filling device 24a that arranges first particles P1 in the concaves of the concave-convex pattern formed on the first base material 11a. The particle arrangement device 1 has a second storage container 21b that stores and supplies the second substrate 11b, and a second belt device 22b that transports the second substrate 11b. The particle arrangement device 1 has a transfer section 25a in which rollers 223a and 223b of the first belt device 22a and the second belt device 22b, respectively, face each other, and the first particles P1 are transferred from the first substrate 11a to the second substrate 11b in the transfer section 25a.

[0074] Furthermore, the particle arrangement device 1 has a second filling device 24b that arranges second particles P2 in a non-transfer portion on the second base material 11b. Note that illustrations and detailed descriptions of devices that are less relevant to explaining the effects of the present invention, such as a peeling and collecting device for peeling and collecting the first base material 11a after transfer from the first belt device 22a and each cleaning device, are omitted.

[0075] In the particle arrangement device 1, the pattern forming device 23, the first filling device 24a, and the transfer unit 25a can be said to be a first arrangement means for arranging the first particles P1 in a pattern on the resin base material which is the second base material 11b. This can be said to be a second arrangement means for arranging the second particles P2 in areas on the oil base material where the first particles P1 are not arranged.

[0076] Hereinafter, a method for arranging particles on substrate 11 using particle arrangement device 1 will be described following the flow of each process. First, the first substrate 11a is supplied from the first storage container 21a to the first belt device 22a by a supplying means (not shown). When the ultraviolet-curable liquid is applied by a pattern forming device 23 (described later), it is preferable that at least the surface of the first base material 11a is made of a material that has high wettability with the ultraviolet-curable liquid. In addition, it is preferable that the surface of the first base material 11a is smooth.

[0077] The first substrate 11a may be a sheet made of a resin such as polyester that has been subjected to a hydrophilic or lipophilic treatment according to the ultraviolet-curable liquid (water-based or oil-based) to be used. The first substrate 11a may be a substrate that is individually cut like cut paper, a continuous substrate wound in a roll like roll paper, or a continuous substrate that is alternately folded like continuous paper.

[0078] The first belt device 22a transports the supplied first base material 11a to a pattern forming position of the pattern forming device 23. The first belt device 22a has driving rollers 221a and 222a, a pressure roller 223a, and a belt-like transport member 224a suspended between them. At this time, the pressure roller 223a is rotated by being driven.

[0079] The conveying member 224a is preferably made of resin or metal, and may be, for example, a polyimide resin belt. The driving rollers 221a and 222a are preferably made of metal, and may be, for example, stainless steel metal rollers. The pressure roller 223a is preferably a soft roller having an elastic layer on its surface, and may be, for example, a soft roller having a silicone rubber elastic layer on the surface of a stainless steel core.

[0080] 2, the first belt device 22a is used as a conveying device for conveying the first base material 11a, but a roller device may be used instead of the belt device. The same applies to the second belt device 22b described later.

[0081] The pattern forming device 23 forms a fine concave-convex pattern on the first base material 11a transported to the pattern forming position. Methods for forming the concave-convex pattern include a UV imprint method, a thermal imprint method, a UV inkjet method, a printing method, and a laser etching method.

[0082] When the pattern forming device 23 forms a concave-convex pattern by the UV imprint method, the pattern forming device 23 has a coating means for coating an ultraviolet-curable liquid on the first base material 11a. As the ultraviolet-curable liquid, for example, an ultraviolet-curable resin such as an ultraviolet-curable liquid silicone rubber can be used. The pattern forming device 23 also has an imprinting means for imprinting a mold having a concave-convex pattern formed on its surface onto the ultraviolet-curable liquid on the first base material 11a, and a light source for irradiating the ultraviolet-curable liquid with ultraviolet rays. Typically, an ultraviolet-curable liquid silicone rubber (PDMS) or resin is used as the ultraviolet-curable liquid, a film mold is used as the mold, and a UV lamp is used as the light source.

[0083] The first filling device 24a fills the first particles P1 with a support material S1 carrying the first particles P1. When P1 is filled into the recesses on the first base material 11a, the opening diameter (width) of the recesses in the concave-convex pattern on the first base material 11a is preferably larger than the cumulative 50% particle diameter (median diameter) based on volume of the first particle P1. Also, the opening diameter (width) of the recesses is preferably smaller than the average size of the support material S1. Here, the opening diameter of the recesses in the concave-convex pattern is preferably the opening diameter in the short side direction of the recesses, and more preferably the maximum opening diameter in the short side direction of the recesses. The width of the recess can be appropriately adjusted depending on the particle sizes of the first particles P1 and the support material S1, etc. The width of the recess is not particularly limited, but is preferably, for example, 0.2 to 30 μm, and more preferably 2 to 15 μm.

[0084] By setting the opening diameter of the recesses of the uneven pattern as described above, the first particles P1 can contact the bottom and side (typically the bottom) of the recesses of the uneven pattern. On the other hand, the support material S1 cannot contact the bottom and side of the recesses. This allows the first particles P1 that contact the bottom and side of the recesses to be captured by the uneven pattern, while the support material S1 can be prevented from being captured by the uneven pattern. In other words, it is preferable that the first particles P1 can contact the bottom and side of the recesses of the uneven pattern, and the first support material S1 cannot contact the bottom and side of the recesses of the uneven pattern.

[0085] Although the pattern forming device 23 forms an uneven pattern on the first substrate 11a, a substrate on which an uneven pattern has been formed in advance on its surface may be used as the first substrate 11a. Alternatively, the pattern forming device 23 may directly form an uneven pattern on the surface of the transport member 224a of the first belt device 22a, or a transport member having an uneven pattern on its surface may be used as the transport member 224a. In this case, in consideration of durability, it is preferable to use a metal belt such as stainless steel or aluminum, and form an uneven pattern on the surface by a micromachining technique such as laser etching, wet etching, or dry etching.

[0086] The first base material 11a having the concave-convex pattern formed on its surface is transported by the first belt device 22a to the filling position of the first filling device 24a. 3 is a diagram showing a schematic configuration of the filling device. The configuration of the first filling device 24a will be described below, but the same applies to the second filling device 24b.

[0087] The first filling device 24a has a filling container 242a that contains a filler 241a, a stirring screw member 243a that stirs and conveys the filler 241a, a recovery member 244a that recovers the filler, and a magnetic member 247a.

[0088] The filler 241a has first particles P1 and a support material S1 that supports the first particles P1. The filler 241a is a mixture of multiple powders including a powder composed of multiple first particles P1 and a powder composed of multiple support materials S1. The filler 241a contained in the filling container 242a is sufficiently mixed when stirred and transported by the stirring screw member 243a. As a result, the first particles P1 are supported on the surface of the support material S1. The force acting between the particles when supported includes, in addition to electrostatic force due to frictional charging, van der Waals force, liquid bridge force, etc.

[0089] The support material S1 is a magnetic particle. The support material S1 is preferably a particle in which the surface of a resin particle in which ferrite core particles or a magnetic body is dispersed is coated with a resin composition. For example, a standard carrier (Standard Carrier P02 manufactured by the Imaging Society of Japan), which is a magnetic particle, can be used. The particle size and material of the support material S1 are appropriately selected according to the particle size and material of the first particles P1. This allows the support material S1 to stably support the first particles P1. In addition, even if the first particles P1 have a small particle size and tend to aggregate, the support material S1 plays a role of loosening the particles by stirring and transporting them. The particle size of the support material S1 can be appropriately adjusted by changing the size (area, width, depth) of the recess. For example, the volume-based cumulative 50% particle size (median diameter) is preferably 50 to 100 μm.

[0090] Recovery member 244a has roller 245a rotatable in the direction of arrow d2 in the figure, and magnet 246a arranged inside roller 245a and fixed to filling container 242a. Magnetic member 247a is arranged facing filling container 242a via transport member 224a, and has magnet 248a inside.

[0091] The magnet 246a has a plurality of N poles and S poles arranged alternately along the rotation direction of the recovery member 244a. The magnet 248a has a plurality of N poles and S poles arranged alternately along the transport direction of the transport member 224a. The magnet 246a has a magnetic pole (N1 pole in FIG. 3) of a different polarity at a position closest to and facing the most downstream magnetic pole (S1 pole in FIG. 3) of the magnet 248a, and an N2 pole of the same polarity as the N1 pole is arranged at the most downstream position. The magnet 246a and the magnet 248a may be composed of a plurality of magnets, and the type of magnets constituting the magnet 246a and the magnet 248a is not particularly limited. For example, a permanent magnet such as a rare earth magnet, a ferrite magnet, a neodymium magnet, a samarium-cobalt magnet, or a plastic magnet, or a means for generating a magnetic field such as an electromagnet can be used. The magnet 248a may be configured to be movable in the transport direction of the first base material 11a or in the opposite direction.

[0092] In addition, a regulating member for regulating the filler 241a on the first base material 11a or a collecting member for re-collecting the filler 241a that cannot be collected by the collecting member 244a may be provided upstream or downstream of the collecting member 244a in the transport direction of the transport member 224a. As the collecting member for re-collecting, in addition to a member similar to the collecting member 244a, a simple member such as a fixed magnet or a regulating member, or a collecting member that collects by air blowing can be used.

[0093] Next, the process of filling the recesses on the first base material 11a with the first particles P1 by the first filling device 24a will be described with reference to FIGS. As the first conveying member 224a moves in the direction of the solid arrow d1 in FIG. 3, the first base material 11a carried and conveyed by the first conveying member 224a is conveyed to the filling position of the first filling device 24a.

[0094] The filler 241a is transported by the stirring screw member 243a and supplied onto the first substrate 11a (dotted line a in FIG. 3). At this time, a magnetic field is formed by the magnetic member 247a and the recovery member 244a, and the filler 241a containing the support material S1, which is a magnetic particle, forms a plurality of magnetic chains on the first substrate 11a due to the magnetic field. The filler 241a supplied onto the first substrate 11a is transported on the first substrate 11a while forming magnetic chains as the first substrate 11a moves (dotted line b in FIG. 3).

[0095] 4A, 4B, and 4C are schematic diagrams of the filler 241a being transported on the first substrate 11a. For the sake of explanation, the filler 241a other than the filler forming one magnetic hair is omitted from the illustration. As described above, the filler 241a on the first substrate 11a forms a magnetic hair along the magnetic field lines of the formed magnetic field, and is transported while changing the shape of the magnetic hair as shown in FIG. 4A, FIG. 4B, and FIG. 4C with the movement of the first substrate 11a. At this time, since a particularly strong magnetic force acts in the vicinity of the magnet 248a, the transport speed v2 of the filler 241a is smaller than the moving speed v1 of the first substrate 11a when the filler 241a moves away from the magnetic pole, and is larger in the opposite case. That is, the filler 241a on the first substrate 11a has a relative speed that is not 0 with respect to the first substrate 11a.

[0096] Fig. 5 is an enlarged view of the vicinity of the surface of the first base material 11a in Figs. 4A to 4C. Although not shown in Figs. 4A to 4C, as shown in Fig. 5, the first base material 11a has a concave-convex pattern 1. The concave and convex pattern can be formed as a desired pattern such as a honeycomb pattern or a line pattern. The filler 241a comes into contact with the concave-convex pattern 111a, and is transported together with the first substrate 11a while being subjected to a magnetic force (solid line Fm in the figure) in a direction perpendicular to the surface of the first substrate 11a and having a non-zero relative speed with respect to the first substrate 11a. As a result, the first particles P1 supported on the support material S1 are transported while being rubbed against the concave-convex pattern 111a on the surface of the first substrate 11a.

[0097] At this time, the particle size of the first particles P1 is smaller than the opening diameter of the recesses of the uneven pattern 111a, and the particle size of the first support material S1 is larger than the opening diameter of the recesses, so the first particles P1 can contact the bottom surface (bottom part) and side parts of the recesses of the uneven pattern 111a, but the support material S1 cannot. That is, only the first particles P1 in the filler 241a selectively contact the bottom surface and side parts of the recesses.

[0098] The first particles P1 that come into contact with the recesses are strongly bound by a physical binding force due to the structure of the concave-convex pattern 111a and non-electrostatic adhesive forces such as electrostatic adhesion and adhesive force between the first base material 11a and the structural material that constitutes the concave-convex pattern 111a, and are detached from the support material S1. Note that, for the sake of explanation, in Fig. 5, the first particles P1 are supported on the surface of the support material S1, but when the filler 241a is stirred, supplied, or transported, there may be particles P1 that are not supported by the support material S1.

[0099] Downstream of the magnetic member 247a, the recovery member 244a is disposed with a gap between it and the first transport member 224a, as shown in Fig. 3. As the first base material 11a moves, the filler 241a transported to the vicinity of the most downstream magnetic pole (pole S1) of the magnet 248a moves from the first base material 11a to the recovery member 244a under the influence of the magnetic field formed by the magnet 246a, and is recovered (dotted line c in Fig. 3).

[0100] As described above, in the transport process (dotted lines a, b, and c in FIG. 3), the recesses of the concave-convex pattern 111a on the surface of the first base material 11a are in sufficient contact with the plurality of fillers 241a. Therefore, the first particles P1 are selectively and densely arranged in the recesses of the concave-convex pattern 111a after the fillers 241a are collected by the collection member 244a.

[0101] 4A to 4C and 5, the first particles P1 are all shown with the same particle size, but in reality there is a particle size distribution, and depending on the material, they may form secondary particles by agglomeration. Also, they may not be spherical as shown. Even in such cases, only particles that can contact the recesses of the uneven pattern 111a are selectively densely packed, so that coarse powder and secondary particles that may adversely affect the particle arrangement process are easily excluded.

[0102] In this way, the amount of the first particles P1 filled in the recesses of the concave-convex pattern 111a can be controlled by the size (area, width, depth) of the concave-convex pattern and the particle size of the first particles P1. Specifically, the area of ​​the recesses is approximately the filled area, and the layer thickness of the filled first particles P1 is determined by the depth of the recesses. The pitch of the convex portions is not particularly limited, but is preferably, for example, 1.0 to 20 μm, and more preferably 2.0 to 15 μm. The height of the convex portions is not particularly limited, but is preferably, for example, 0.1 to 20.0 μm, and more preferably 1.0 to 10.0 μm. The area ratio of the recesses (the ratio of the recesses to the area of ​​the recessed and concave pattern) is not particularly limited, but is preferably, for example, 50% or more, and more preferably 70% or more.

[0103] For example, to obtain a thin layer (single layer) that is 50% of the substrate area, the area ratio of the recesses (concave-convex pattern) is The area ratio of the recesses to the entire turn should be controlled to 50%, and the depth of the recesses should be controlled to the particle size of the first particles P1 or less. In this case, the opening width of the recesses should be set to be larger than the median diameter of the first particles P1 and smaller than the average size of the support material S1 (here, the average particle size).

[0104] The first particles P1 may have a wide particle size distribution, but the support material S1 preferably has a narrow particle size distribution, and more preferably is monodisperse. This makes it easier to prevent the support material S1 from contacting the bottom (or bottom surface) or side of the recess. If the support material S1 can contact the bottom or side of the recess, the support material S1 may be restrained and filled in the recess.

[0105] Furthermore, the opening width of the recesses of the uneven pattern 111a is preferably smaller than four times the particle diameter of the first particles P1. By making the opening width smaller than four times the particle diameter of the first particles P1, the probability that the first particles P1 will come into contact with two points, the bottom and side surfaces of the recesses of the uneven pattern 111a, can be increased. In this way, the first particles P1 that come into contact with the uneven pattern 111a at multiple points are strongly constrained by the uneven pattern 111a, and therefore the efficiency of filling the uneven pattern 111a with the first particles P1 can be increased. The same applies to the particle size of the second particles P2 described later and the size of the recesses of the uneven pattern formed by the first particles P1 on the second base material. In addition, when brush fibers are used as the support material, the "average particle size of the support material" in the above explanation becomes the "average fiber diameter of the support material."

[0106] The filler 241a collected by the collecting member 244a is transported by the roller 244a which is a rotating collecting member (dotted line in FIG. 3 d). The filler 241a transported by the roller 244a falls into the filling container 242a (dotted line in FIG. 3 e) due to the magnetic field of two adjacent and repelling same-polarity magnetic poles (N1, N2) and the influence of gravity. Thereafter, the filler 241a is stirred and transported again by the stirring screw member 243a, and this process is repeated thereafter.

[0107] The weight ratio of the first particles P1 and the support material S1 in the filler 241a in the filling container 242a is determined by an inductance sensor that measures using magnetic permeability, a patch concentration sensor that measures and predicts the reflection density on a substrate, etc., which are common in electrophotographic devices. At least one of the first particles P1 and the support material S1 is replenished by a replenishing means (not shown) as necessary. This allows stable filling over a long period of time. The mass % of the first particles P1 in the filler 241a is not particularly limited, but is preferably in the range of 5 to 40 mass %, or 10 to 30 mass %.

[0108] Although the filling device described here uses magnetic particles as a carrier material to form a so-called magnetic brush, the type of filling device is not limited to this. Brush fibers can also be used as the carrier material. Alternatively, an elastic material, at least the surface of which is made of an elastic body, can also be used as the carrier material.

[0109] FIG. 6A is a diagram showing a schematic configuration of a filling device 24c in the case where brush fibers are used as the support material. The filling device 24c has a roller 2410 having brush fibers on its surface. The roller 2410 is a so-called brush roller, with brush fibers planted on its surface. The material of the fibers constituting the brush fibers of the roller 2410 may be, for example, nylon, rayon, acrylic, vinylon, polyester, or vinyl chloride. The surface of the fibers may be subjected to a surface treatment in order to adjust the electrostatic charge property or rigidity.

[0110] The filling device 24c has a supplying member that supplies the filler 241a to the roller 2410. The filler 241a includes powder including the first particles P1, and is stored in a filling container 242a. In this example, the filler 241a does not include the support material S1, which is magnetic particles. The filler 241a is agitated and conveyed by the agitating screw member 243a, and is supplied to the supply member 249.

[0111] The supply member 249 is a member that supplies the filler 241a to the roller 2410, and its configuration is not particularly limited. For example, the supply member 249 can be a roller having at least a surface made of a porous foam material having elasticity. Typically, an elastic sponge roller having a foamed skeletal structure and having a relatively low hardness polyurethane foam formed on a core metal can be used. Note that, in addition to urethane, various rubber materials such as nitrile rubber, silicone rubber, acrylic rubber, hydrin rubber, and ethylene propylene rubber can be used as the material of the foam material.

[0112] The supplied filler 241a is filled into the foam material on the surface of the supply member 249, and is transported to a supply section that comes into contact with the roller 2410. In the supply section, the filler 241a filled into the foam material is charged by contact with the brush fibers of the roller 2410, and is carried by the brush fibers of the roller 2410. Furthermore, the supply member 249 may also have a function of peeling off the filler 241a remaining on the roller 2410 and refreshing it. The filler 241a supplied to the roller 2410 comes into contact with the first base material 11a by the movement of the brush fibers.

[0113] At this time, the first particles P1 in the filler 241a can contact the bottom and side surfaces of the recesses of the uneven pattern 111a on the surface of the first base material 11a, but the brush fibers cannot. That is, the fiber diameter of the brush fibers is made larger than the opening width of the recesses of the uneven pattern 111a. The fiber diameter of the brush fibers can be measured by placing glass on the surface of the roller 2410 and taking an image of the brush fibers through the glass using an optical microscope. At this time, the fiber diameters of about 100 brush fibers are measured, and the distribution of the fiber diameters is measured to calculate the average diameter.

[0114] The movement of the transport member 224a and the rotation of the roller 2410 cause the brush fibers of the roller 2410 to rub against the surface of the first base material 11a. As a result, the first particles carried by the brush fibers are densely arranged in the recesses of the uneven pattern 111a on the surface of the first base material 11a.

[0115] FIG. 6B is a diagram showing a schematic configuration of a filling device 24d when an elastic material is used as the support material. The filling device 24d has a similar configuration to the filling device 24c, but differs in that a roller 2411 having an elastic material is used instead of the roller 2410 having brush fibers. The roller 2411 is a roller having an elastic layer formed on its surface.

[0116] The elastic layer is formed of a material having elasticity, such as a rubber material, such as silicone rubber, acrylic rubber, nitrile rubber, urethane rubber, fluororubber, etc. The surface shape of the elastic layer may be controlled by adding fine particles, such as spherical resin particles. When the elastic layer has a convex portion on its surface, the size of the convex portion of the elastic layer is set to be larger than the size of the concave portion of the concave-convex pattern 111a. The size of the convex portion of the elastic layer can be measured in the same manner as the fiber diameter of the brush fiber described above.

[0117] The movement of the transport member 224a and the rotation of the roller 2411 causes the elastic material on the surface of the roller 2411 to rub against the surface of the first base material 11a. As a result, the first particles supported by the elastic material are densely arranged in the recesses of the concave-convex pattern 111a on the surface of the first base material 11a.

[0118] By using brush fibers or elastic materials as the carrier material as in Figures 6A and 6B, it is not necessary to include magnetic particles in the filler. In addition, the configuration of the filling device can be simplified. On the other hand, when magnetic particles are used as the carrier material as in Figure 3, there is a higher degree of freedom in the size and shape of the carrier material than in the case of brush fibers or elastic materials. In addition, the carrier material can move more freely on the substrate when magnetic particles are used.

[0119] For these reasons, when magnetic particles are used as the support material, the particles such as the first particles P1 can be more efficiently supplied onto the substrate, and the recesses on the substrate can be more efficiently filled. Also, when a magnetic material is used as the support material, even if the support material deteriorates during the process, the support material can be replenished or replaced without stopping the process.

[0120] The method of filling the recesses with particles by rubbing the support material carrying the particles allows a larger amount of dispersed particles to be supplied to the recesses, and allows for stable and dense filling, compared to a filling method using a restricting member such as a blade. This advantage is more pronounced as the particle size of the particles to be filled becomes smaller, since the particles tend to aggregate.

[0121] The first base material 11a, in which the concaves of the concave-convex pattern 111a have been filled with the first particles 1 by the first filling device 24a, is transported to the transfer section 25a by the first belt device 22a. 2, the second belt device 22b has driving rollers 221b and 222b, a pressure roller 223b, and a belt-like conveying member 224b suspended therebetween, similar to the first belt device 22a. At this time, the pressure roller 223b is driven to rotate. At the transfer section 25a, the pressure roller 223a of the first belt device 22a and the pressure roller 223b of the second belt device 22b face each other.

[0122] The second substrate 11b is supplied from the second storage container 21b to the second belt device 22b and transported in the direction of the arrow in Fig. 2. The supplied second substrate 11b is transported in accordance with the timing at which the first substrate 11a is transported to the transfer section 25a. In the transfer section 25a, the first particles P1 filled in the first substrate 11a are transferred to the second substrate 11b.

[0123] That is, the first substrate 11a can be called a transfer substrate for transferring the first particles P1 to the second substrate 11b. The concave-convex pattern formed on the surface of the first substrate 11a can be called a transfer concave-convex pattern. Hereinafter, this transfer process will be described with reference to FIG. 7.

[0124] 7 is a diagram showing a schematic configuration of the transfer unit 25a. The transfer unit 25a is composed of the pressure roller 223a and the conveying member 224a of the first belt device 22a, and the pressure roller 223b and the conveying member 224b of the second belt device 22b. As described above, the pressure rollers 223a and 223b rotate drivenly, and the two rollers are in contact with each other via the conveying members 224a and 224b. At least one of the pressure rollers 223a and 223b is a soft roller having an elastic layer on its surface, and a nip portion is formed at the portion where the two rollers are in contact with each other.

[0125] The first substrate 11a filled with the first particles P1 by the first filling device 24a and the second substrate 11b are transported at substantially the same speed by the respective transport members (224a, 224b) and enter a nip portion formed by contact between the pressure rollers 223a, 223b. In the nip portion, the first particles P1 on the first substrate 11a come into contact with the second substrate 11b and are transferred onto the second substrate 11b.

[0126] The adhesive force of the second substrate 11b to the first particles P1 is greater than that of the first substrate 11a. The adhesive force of the first particles P1 to the second substrate 11b is greater than the adhesive force of the first particles P1 to the first substrate 11a. In other words, the adhesive force of the first particles P1 to the second substrate 11b is greater than the adhesive force of the first particles P1 to the first substrate 11a. As a result, the first particles P1 on the first substrate 11a are transferred onto the second substrate 11b at the nip portion.

[0127] The material of the second substrate 11b is not particularly limited, and a substrate made of the same material as the first substrate 11a can be used. Note that, like the first substrate 11a, the second substrate 11b may be a substrate that is individually cut off like cut paper, a continuous substrate that is wound into a roll like roll paper, or a continuous substrate that is alternately folded like continuous paper.

[0128] The second substrate 11b is preferably subjected to a surface treatment for increasing adhesion in order to transfer the contacted first particles P1. For example, the second substrate 11b preferably has an adhesive portion on its surface where an adhesive is applied. As a preparation step for preparing a resin substrate having an adhesive portion, for example, the second substrate 11b is prepared. The thickness of the second substrate is not particularly limited, but is preferably, for example, 1 to 10 μm. The thickness of the adhesive portion is not particularly limited, but is preferably, for example, 0.1 μm or more, and more preferably, 0.5 μm or more.

[0129] Furthermore, the back surface of the second base material 11b (the surface to which the first particles P1 are not transferred) also has an adhesive portion coated with the same adhesive as the front surface, and the front surface is preferably covered with a protective film or the like. This prevents the base materials from shifting when stacking as described below, and the active material particles and electrolyte particles between the base materials are sandwiched between the top and bottom surfaces (stacking direction) and firmly fixed. This prevents the particles from moving during stacking, storage of the stack, heat treatment, and pressure application, and allows the desired electrode precursor to be formed.

[0130] The adhesive is not particularly limited, and may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, or a thermoplastic resin or a photocurable resin whose adhesive strength changes due to disturbances such as heat or light. Furthermore, the particle arrangement device 1 may have an application means such as a dispenser or an inkjet head that applies an adhesive to the surface of the second base material 11b during transportation. The type and amount of adhesive applied are appropriately adjusted depending on the shape and material of the concave-convex pattern used, and the particle size and material of the first particles P1 and the second particles P2, but it is preferable that the adhesive has a stronger adhesive strength than the concave-convex pattern 111a. Comparison of adhesive strengths can be measured by a general method using a nanoindenter.

[0131] In the nip portion, the first particles P1 are restrained by an adhesive force generated between the first particles P1 and the second substrate 11b. When the conveying members 224a and 224b pass the nip portion and are separated from each other, the first particles P1 on the first substrate 11a are transferred to the second substrate 11b.

[0132] The second base material 11b onto which the first particles P1 have been transferred is transported by the transport member 224b to the filling position of the second filling device 24b. The second filling device 24b has the same configuration and function as the first filling device 24a, except that a filling material 241b having second particles P2 and a support material S2 is contained in a filling container 242a instead of a filling material 241a having first particles P1 and a support material S1.

[0133] The second filling device 24b fills the second particles P2 into the portion of the second substrate 11b where the first particles P1 are not arranged. As described above, the first particles P1 are arranged on the second substrate 11b that has passed through the transfer unit 25a, but the adhesive portion is exposed in the portion where the first particles P1 are not arranged, and a recess is formed, so to speak. The second filling device 24b fills this recess (adhesive portion) with the second particles P2 in a process similar to that of the first filling device 24a. .

[0134] In this manner, the second particles P2 that can be filled are selectively filled into gaps on the second base material 11b where the first particles P1 are not arranged, thereby improving the coverage rate of the base material by the particles. The second particles P2 preferably have a median diameter equal to or smaller than the opening width of the gap between the first particles P1. Note that, although the case where magnetic particles are used as the carrier material will be described here, brush fibers or elastic material may be used as the carrier material, as in the first filling device 24a.

[0135] The filler 241b has second particles P2 and a support material S2 that supports the second particles P2. The filler 241b is a mixture of multiple powders including a powder composed of multiple second particles P2 and a powder composed of multiple support materials S2. The support material S2 may be the same as the support material S1 or may be different. It is appropriately selected according to the particle size and material of the second particles P2 and the opening width of the above-mentioned void portion. The mass % of the second particles P2 in the filler 241b is not particularly limited, but is preferably in the range of 5 to 40 mass %, or 10 to 30 mass %.

[0136] FIG. 8 is an enlarged view of the vicinity of the surface of the second substrate 11b in the filling process by the second filling device 24b. On the second substrate 11b, an uneven pattern is formed having convex portions formed by arranging the first particles P1 and concave portions where the first particles P1 are not arranged. The adhesive portion 13b is exposed in the concave portion on the second substrate 11b where the first particles P1 are not arranged. In the filling process by the second filling device 24b, the second particles P2 are arranged on the adhesive portion 13b on the surface of the second substrate 11b. After the filling process by the second filling device 24b, the first particles P1 and the second particles P2 are arranged adjacent to each other on the surface of the adhesive portion of the second substrate 11b. That is, the first particles P1 and the second particles P2 can be arranged adjacent to each other by arranging the second particles P2 on the portion on the second substrate 11b where the first particles P1 are not arranged. Furthermore, it is not necessary that the second particles P2 are disposed adjacent to all of the first particles P1, and the first particles P1 or the second particles P2 may be adjacent to each other.

[0137] The filler 241b comes into contact with this uneven pattern, and is transported together with the second substrate 11b while having a non-zero relative speed with respect to the second substrate 11b, while being subjected to a magnetic force (solid line Fm in the figure) in a direction perpendicular to the surface of the second substrate 11b. As a result, the second particles P2 supported by the support material S2 are transported while being rubbed against the uneven pattern on the surface of the second substrate 11b.

[0138] At this time, the opening width of the recesses of the uneven pattern is set to a size that allows the second particles P2 to contact the recesses but not the support material S2. That is, the opening diameter of the recesses of the uneven pattern on the second base material 11b is preferably larger than the cumulative 50% particle size (median diameter) in the volume-based particle size distribution of the second particles P2. Also, the opening diameter of the recesses is preferably smaller than the average size of the support material S2. Here, the opening diameter of the recesses of the uneven pattern is preferably the opening diameter in the short side direction of the recesses, and more preferably the maximum opening diameter in the short side direction of the recesses. This allows only the second particles P2 in the filler 241b to selectively contact the recesses.

[0139] The second particles P2 that come into contact with the recesses are strongly bound by the physical binding force due to the structure of the concave-convex pattern, and by electrostatic adhesion and adhesive force with the second base material 11b and the structural material that constitutes the concave-convex pattern (here, the first particles P1), and are detached from the support material S2. Note that, for the sake of explanation, in FIG. 8, the second particles P2 are supported on the surface of the support material S2, but when the filler 241b is stirred, supplied, or transported, there may be second particles P2 that are not supported by the support material S2. stomach.

[0140] 9A is a schematic diagram of the second substrate 11b after the first particles P1 are transferred by the transfer unit 25a, and is a diagram of the second substrate 11b viewed from a direction perpendicular to the substrate surface. As shown in FIG. 9A, a honeycomb pattern is formed on the second substrate 11b, in which the arrangement regions in which the first particles P1 are arranged in a regular hexagonal shape are aligned.

[0141] The first particles P1 are densely arranged within this regular hexagonal region, and the first particles P1 are not arranged in other parts (white parts in FIG. 9A), and the adhesive part of the surface of the second base material 11b is exposed. The regular hexagonal region in which the first particles P1 are held is another way of saying the first pattern part. Moreover, the honeycomb pattern region in which the second particles P2 are held and which corresponds to the gaps in the first pattern part is another way of saying the second pattern part.

[0142] FIG. 9B is a schematic diagram of the second substrate 11b after the second particles P2 are filled by the second filling device 24b, and is a view of the second substrate 11b viewed from a direction perpendicular to the substrate surface. As shown in FIG. 9B, the second particles P2 are densely arranged in the region where the first particles P1 are not arranged and the adhesive portion is exposed. Also, the first particles P1 and the second particles P2 are densely arranged in the boundary between the region where the first particles P1 are arranged and the region where the second particles P2 are arranged. Note that the particles can be filled in the small gaps between the first particles P1 in a similar manner. In this case, it is possible to fill in the gaps between the first particles P1 in a similar manner to the above, using a filler containing particles with a particle size equivalent to the gaps between the first particles P1, and a more dense thin film can be formed.

[0143] Although the first particles P1 and the second particles P2 are arranged by one filling device 24a and 24b, multiple filling devices may be used. This can improve the compactness. In addition, the particles are not limited to the first particles P1 and the second particles P2, and a third particle other than the first particles and the second particles can be arranged by adding a filling device.

[0144] [Particle placement device 2] 10 is a diagram showing a schematic configuration of the particle arrangement device 2. The particle arrangement device 2 is a device for forming a particle layer 12 on the substrate 11, and includes a storage container 21 for storing and supplying the substrate 11, and a belt device 22 for transporting the substrate 11. The particle arrangement device 2 may also include a liquid application device 201 for applying a liquid for providing an adhesive portion on the substrate 11. In this case, in order to densely arrange the particles on the substrate 11, it is preferable to apply the liquid in a pattern on the substrate 11.

[0145] As the liquid applying device 201, a device that ejects liquid by an inkjet method or a device that applies liquid can be used, but a plate-based method such as a flexographic plate can also be used. Among them, it is preferable to use a device that ejects liquid by an inkjet method as the liquid applying device. As a device for discharging liquid by the inkjet method, devices using various discharging methods, such as a thermal type, a piezoelectric type, an electrostatic type, and a continuous type, can be used.

[0146] The liquid applied by the liquid applying device 201 may be water-based or oil-based as long as it contains a material to which the first particles P1 can be attached. The liquid is appropriately selected, for example, by selecting a material that does not react with the first particles P1. The liquid applying device 201 may also form the pattern L1 with a plurality of types of liquid. For example, the liquid applying device 201 may apply two types of liquid that react with each other on the substrate 11 to increase adhesion. Examples of materials to which the first particles P1 can be attached include resins such as acrylic resins.

[0147] The powder applying device 202 applies a powder containing the first particles P1 to the substrate 11 on which the liquid has been arranged in a pattern. As a result, the first particles P1 are fixed by the material on the substrate 11, and the particles P1 are fixed in a pattern corresponding to the pattern L1.

[0148] The means for applying the powder by the powder applying device 202 may be a means for spraying or sprinkling the powder toward the substrate 11. The powder applying device 202 may further include a means for removing the first particles P1 that are not fixed to the substrate 11 by means of vibration, centrifugation, air blowing, suction, or the like.

[0149] The particle arrangement device 2 may further include a drying device that evaporates at least a part of the liquid applied by the liquid application device 201 to control the amount of material on the substrate 11, the thickness of the pattern L1, and the like. This drying device may be provided downstream of the liquid application device 201 and upstream of the powder application device 202. The material on the substrate after drying may be a liquid, a liquid containing solids, or only solids.

[0150] After the first particles P1 are fixedly arranged on the substrate 11, a liquid is arranged by a liquid applicator 203 to provide an adhesive portion at least in the area where the first particles P1 were not arranged. The liquid applicator 203 has the same function as the liquid applicator 201. The second particles P2 are arranged on the substrate 11 to which the liquid has been applied by the liquid applicator 203, using a second filling device 24. As a result, a dense particle layer 12 is formed on the substrate 11.

[0151] Similarly to the particle arrangement device 1, the particle arrangement device 2 may have a transfer unit. In this case, the transfer unit is provided downstream of the powder applicator 202. The first particles P1 are transferred from the substrate 11 to another substrate having an adhesive portion. In the substrate to which the first particles P1 have been transferred, the second particles P2 can be arranged by using the second filling device 24 in the region where the first particles P1 are not arranged and the adhesive portion is exposed. This makes it possible to arrange the first particles P1 and the second particles P2 densely on the adhesive portion of the resin substrate.

[0152] In the particle arrangement devices 1 and 2, the coverage of the resin substrate by the first particles P1 and the second particles P2 is preferably 60% or more, more preferably 70% or more, and even more preferably 80% or more. The coverage of the resin substrate by the first particles P1 and the second particles P2 can be measured by photographing the region where the particle layer is formed from the substrate vertical direction using an optical microscope and calculating the area ratio of the first particles P1 and the second particles P2 in the region using image processing software.

[0153] By using the above-mentioned particle arrangement device 1 or particle arrangement device 2, the first particles P1 are arranged on the adhesive portion of the resin substrate in the first step (S101 in FIG. 1) of FIG. 1, and the second particles P2 are arranged.

[0154] (2nd process) The second step is a step of forming a laminate by laminating a plurality of resin base materials (hereinafter also referred to as base materials) on which particle layers are formed. The number of layers of the laminate is not particularly limited and is determined according to the desired electrode capacity. In addition, the laminate is preferably formed on a current collector such as a positive electrode current collector as a substrate. That is, the laminate preferably includes a substrate. As the current collector, a known current collector such as an Al foil, a SUS foil, a platinum foil, or a gold foil can be used. An electrolyte may be used as the substrate.

[0155] In this case, the electrolyte may be a separately prepared solid electrolyte sheet or an electrolyte substrate consisting of electrolyte particles on a similar substrate. A solid electrolyte may be used as the electrolyte. When the electrode is a positive electrode, the solid electrolyte sheet or electrolyte substrate may be a substrate of a positive electrode substrate. A negative electrode or a negative electrode substrate may be formed on the side opposite to the lamination surface.

[0156] 11 is a diagram showing a schematic configuration of the laminate forming apparatus U3. The laminate forming apparatus U3 has a conveying device 31 that conveys the substrate 11 on which the particle layer 12 is formed, and a stage 32 that can be moved quickly and easily in the vertical direction by an actuator (not shown).

[0157] The conveying device 31 receives the substrate 11 having the particle layer 12 formed using the particle arrangement device, and conveys it to the stage 32. Examples of the conveying device 31 capable of conveying the substrate 11 include a belt conveyor, a roller, and a robot arm. When the substrate 11 is transported to the stage 32 by the transport device 31, the stage 32 moves in the vertical direction by an amount equivalent to the thickness of the substrate 11 and the particle layer 12. By repeating the transport by the transport device 31 and the movement of the stage 32, a plurality of substrates 11 each having a particle layer 12 formed thereon are stacked, and the laminate 15 is formed.

[0158] In this case, it is preferable that the back surface of the substrate 11 on which the particle layer 12 is formed has an adhesive portion. This adhesive portion allows the substrates to adhere to each other, increasing the strength of the laminate and suppressing misalignment between the substrates even after the second step. Furthermore, the particle layer 12 between the substrates is sandwiched between the upper and lower adhesive portions, thereby suppressing misalignment during processing or storage of the laminate. The adhesive portion may be applied by a coating device (not shown) before lamination, or a substrate that has been previously coated may be used, and the protective film coated on the coated surface may be peeled off before lamination to laminate.

[0159] It is preferable to have a static elimination step of eliminating static electricity from the substrate immediately before forming the laminate 15. The particle layer 12 and substrate 11 formed using the particle arrangement device are easily charged, and electrostatic repulsion occurs between the substrates when they are laminated. Therefore, when they are laminated in the second step, the substrates tend to peel off or gaps tend to form between the substrates. In the static elimination step, it is preferable to eliminate static electricity in a non-contact manner using an electrostatic elimination blower or the like. In addition, after the laminate 15 is formed, it is preferable to have a degassing step of degassing the laminate in order to reduce voids between the substrates. In the degassing step, degassing is preferably performed using a vacuum packaging machine or the like.

[0160] (3rd step) The third step is a step of removing the resin substrate from the laminate to form a three-dimensional object including the active material particles and the electrolyte particles. Preferably, the laminate is sintered to remove the resin substrate from the laminate. This allows the active material particles to have an inner surface and an outer surface. That is, the third step can be said to be a step of forming an inner surface on the active material particles, and also a step of forming an outer surface on the active material particles. 12 is a diagram showing a schematic configuration of the sintering apparatus U4. The sintering apparatus U4 has a transport device 41 that transports the laminate 15 and a heating furnace 42 that heats the laminate 15.

[0161] The conveying device 41 receives the laminate 15 from the laminate forming device and conveys it to the heating furnace 42. Like the conveying device 31, the conveying device 41 is preferably a device capable of conveying the laminate 15. Examples of devices capable of conveying the laminate 15 include a belt conveyor, a roller, and a robot arm.

[0162] The heating furnace 42 is a furnace for heating the laminate 15. The heating furnace 42 has a heating means 421, a pressurizing means 422, and an atmosphere adjusting means 423 (423a and 423b). A firing furnace used for firing ceramics or the like can be used as the heating furnace 42. The pressurizing means 422 pressurizes the laminate 15 being heated in the heating furnace 42, and pressurizes the laminate 15 before and after heating.

[0163] In addition, it is preferable that the pressurizing means 422 has a pressurizing portion for pressurizing the laminate 15 formed of a porous material that allows easy passage of gas. The atmosphere adjusting means 423 has an atmosphere gas supplying means 423a and a pressure reducing means 423b, and adjusts the atmosphere gas in the processing space of the heating furnace 42. The atmospheric gas that can be used includes an oxidizing atmosphere (O2), an inert atmosphere (Ar, N2, etc.) and a reducing atmosphere (Ar-H2), but sintering may be performed in air.

[0164] When the laminate is sintered, it is preferable to heat the laminate at a temperature equal to or higher than the thermal decomposition temperature of the base material 11 in the laminate 15, and it is preferable to heat the laminate at a temperature lower than the thermal decomposition temperature of each particle layer in the laminate 15. The temperature to which the laminate is heated is preferably 200°C or higher and 1000°C or lower, more preferably 400°C or higher and 800°C or lower, particularly preferably 450°C or higher and 800°C or lower, and even more preferably 450°C or higher and 650°C or lower. It is preferable to maintain the sintering temperature for 30 minutes or more, and more preferably for 1 hour or more. The upper limit is not particularly limited, but may be, for example, 3 hours or less, or may be 2 hours or less. For example, it is preferable to maintain the sintering temperature for 30 minutes to 3 hours, or 1 hour to 2 hours. The thermal decomposition temperature is the temperature at which the weight of the material starts to decrease when the temperature is gradually increased in the heating atmosphere in the sintering treatment device. Therefore, by heating the laminate at a temperature equal to or higher than the thermal decomposition temperature of the base material 11, the base material 11 in the laminate can be decomposed to reduce its weight, and the base material 11 can be removed from the laminate.

[0165] The heating temperature is preferably equal to or higher than the thermal decomposition temperature of the base material 11, but it is preferable to heat the base material 11 at a temperature higher than the thermal decomposition temperature. Specifically, when the base material 11 is heated from room temperature (25°C) at a rate of 5°C / min in an atmosphere (typically air) during heating in a sintering treatment device and a thermogravimetric analysis is performed, the base material 11 is preferably heated at a temperature equal to or higher than the temperature at which the weight of the base material 11 is reduced to 70% of its initial weight. Specifically, the temperature is preferably 385°C or higher, for example.

[0166] Similarly, when a thermogravimetric analysis is performed, it is more preferable to heat the substrate 11 at a temperature equal to or higher than the temperature at which the substrate 11 loses 50% of its initial weight, and it is even more preferable to heat the substrate 11 at a temperature equal to or higher than the temperature at which the substrate 11 loses 20% of its initial weight. Specifically, for example, the temperature is preferably 400° C. or higher, and more preferably 450° C. or higher. This can shorten the time required to remove the substrate 11 and increase the removal rate of the substrate 11.

[0167] In this way, when the sintering treatment apparatus removes the base material 11 by heating, it is preferable that the active material particles and the solid electrolyte particles have a higher thermal decomposition temperature than the base material 11. In general, inorganic materials tend to have higher thermal decomposition temperatures than organic materials, so it is preferable that the active material particles and the solid electrolyte particles are inorganic materials and the material of the base material 11 is an organic material such as a resin. In addition, when the sintering treatment apparatus removes the base material 11 by heating, it is preferable that the active material particles are a material having a softening point temperature higher than the thermal decomposition temperature of the base material 11.

[0168] The sintering apparatus preferably removes 90% by weight or more of the resin substrate in the laminate 15 by heating, more preferably removes 95% by weight or more, and even more preferably removes 97% by weight or more. At that time, the resin substrate is preferably burned or gasified and released to the outside as a gas. At this time, when the resin substrate gasified by pyrolysis is released to the outside of the laminate as a gas, it may push up the particle layer formed on the resin substrate and distort the shape. For this reason, it is preferable to reduce the thickness of the resin substrate to reduce the effect on the particle layer.

[0169] Specifically, the thickness (μm) of the resin substrate is preferably 10 times or less, more preferably 5 times or less, and even more preferably 2 times or less, of the thickness of the particle layer on the resin substrate. Here, the thickness of the particle layer is defined as the thickness of the resin substrate surface (x, y) and the thickness of the layer in the lamination direction of the resin substrate ( z), it indicates the difference between the maximum and minimum values ​​of z in the region (x, y, z) where each particle arranged on the resin substrate exists.

[0170] The thickness of the particle layer on the resin substrate is calculated by observing the cross section of the laminate 15 with a BIB-SEM, determining the particle presence area (x, z) with image processing software, where the resin substrate surface is x and the lamination direction of the resin substrate is z, and calculating the difference between the maximum and minimum values ​​of z. Here, the BIB-SEM photographing conditions, the required image area, and the image processing method are the same as those described below.

[0171] The thickness of the resin substrate may be determined by BIB-SEM like the particle diameter of the active material particles, or may be measured using a digital thickness gauge, etc. In addition, in SEM observation using BIB-SEM, the active material particles, solid electrolyte particles, substrate, and adhesive portion may be identified by elemental composition analysis using EDS, for example.

[0172] The cross-sectional observation of the electrode is obtained from the two-dimensional image obtained by a scanning electron microscope of the cross-section processed by a broad ion beam (BIB) with Ar. Hereinafter, the above-described method for observing the two-dimensional image is referred to as BIB-SEM. The details of the measurement method will be described later.

[0173] <Imaging method of BIB-SEM> The cross-section of the electrode is imaged by BIB-SEM. The imaging conditions of BIB-SEM are described below. When the electrode is included in the battery, the battery is disassembled and a sample containing the electrode is taken out. For example, in the case of a laminated battery, the lamination is opened and the laminate containing the electrode is taken out. In order to suppress the load of the following cross-section processing, the other current collector and electrode that are unnecessary for imaging are separated from the laminate, and a sample containing the electrode is taken out. The electrode can be specified as the region between the electrolyte layer and the current collector layer. The sample is cut with a wire saw (DWS3400 / wire diameter 170 μm · diamond diameter 30 μm) so as to be a cut surface along the lamination direction. The cross-section is processed with a broad ion beam of Ar (JEOL SM-09010 Cross Section Polisher) on the cut surface. The conditions for cross-section processing are a voltage of 6 kV and a current of 150 to 200 mA. As a BIB-SEM image, a cross-section in the lamination direction of the electrode sample is obtained and cross-section observation is performed. Instead of the broad ion beam (BIB), a fine ion beam (FIB) with changed ion particle intensity and beam diameter in the beam can also be used.

[0174] The cross-section is imaged by an electron microscope (ULTRA55) under the following conditions. Detector: ESB (reflected electron image) Observation conditions: acceleration voltage 3 kV Magnification: 1000 times Filter: Apply a bias of 1500 V to the ESB filter

[0175] Next, elemental and compositional analysis of each particle of the electrode and the conductive resin was performed using a SEM-EDX (XFlash Detector 630M manufactured by Bruker) to distinguish between the active material particles, electrolyte particles, and the conductive resin. The active material particles, electrolyte particles, and conductive resin are identified by the above-mentioned method. The electrode is analyzed by X-ray diffraction (XRD) or the like to identify the materials constituting the electrode. Then, the specific elements contained in each of the active material particles, electrolyte particles, and conductive resin are detected and identified by SEM-EDX by the above-mentioned method. The materials constituting the electrode can also be identified by electron energy loss spectroscopy (EELS) in a TEM, in addition to the above-mentioned X-ray diffraction. They can also be identified by Raman spectroscopy or TOF-SIMS, and the above-mentioned analytical methods may be combined to identify the materials constituting the electrode.

[0176] The thickness of the resin substrate is preferably 1 μm or more and 1 mm or less, and the thickness of the particle layer is preferably 0.1 μm or more and 100 μm or less.

[0177] By using a substrate made of an organic material such as resin as the substrate, it is possible to easily remove the substrate by heating. Materials that can be used to form the substrate include polyesters such as polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET), and polyamides such as nylon. Of these, it is preferable to use PET from the viewpoints of its decomposition temperature and the low toxicity of gases generated during thermal decomposition.

[0178] The sintering apparatus preferably exhausts the released gas to the outside of the heating furnace 42 by the pressure reducing means 423b. The resin base material can be burned and removed by creating an oxidizing atmosphere, i.e., an atmosphere containing oxygen gas such as air, inside the heating furnace 42 by the atmospheric gas supplying means 423a or the like. On the other hand, depending on the active material particles and electrolyte particles used, sintering in an oxidizing atmosphere may cause decomposition or composition change. In such cases, sintering in an inert atmosphere (Ar, N2, etc.) or a reducing atmosphere (Ar-H2) is preferable.

[0179] As described above, when the resin base material is gasified by pyrolysis from the laminate 15 and released as a gas, each particle layer in the laminate 15 may be pushed up and change shape. Therefore, when heating in the heating furnace 42, the laminate 15 may be pressurized by the pressurizing means 422 before or during heating.

[0180] FIG. 13A is a BIB-SEM image of the cross section of the laminate after the second step. It corresponds to a cross section of the laminate 15 in which six lamination units each including a particle layer 12 and a second substrate 11b are laminated on a resin substrate 14 so that the particle layer 12 and the second substrate 11b are alternately laminated. FIG. 13B is a BIB-SEM image of the three-dimensional object 16 after the third step. The resin substrate is removed from the laminate 15, resulting in a three-dimensional object 16 consisting of six particle layers. FIG. 13C is an SEM image of the upper part of the three-dimensional object 16. The first particles P1 and the second particles P2 periodically arranged on the second substrate 11b in the first step are maintained after the second step.

[0181] Fig. 14A is a BIB-SEM image of a three-dimensional object 16 according to one embodiment (Example 1) of the present disclosure, and Fig. 14B is an enlarged image of Fig. 14A. A three-dimensional object 16 is formed by the manufacturing method of the present disclosure using positive electrode active material particles LiCoO2 (hereinafter, LCO) as the first particles P1 and electrolyte particles Li3BO3 (hereinafter, LBO) as the second particles P2. In this embodiment, the LCO particles (first particles P1) have a core portion P1a, a shell portion P1b, and radially protruding portions P1c on the surface of the shell portion, as shown in FIGS. 14A and 14B. A gap portion P1d exists between the core portion and the shell portion. In FIG. 14B, P1d is an internal hole in the active material particle that communicates with the outer surface of the active material particle, and can also be called a communication hole 19-1. The LCO particles also have an inner surface 19 as shown by a solid line.

[0182] A presumed mechanism for how the three-dimensional object 16 has the above-described configuration in this embodiment will be described with reference to Figs. 15 to 18-1 and Figs. 18-2A to 2D. FIG. 15A shows an example of a temperature profile in each step (S101 to S104) of the manufacturing method of an electrode precursor according to the present disclosure, and a profile showing the redox behavior depending on the atmosphere. FIG. 15B is a schematic diagram showing the change in the LCO particles in the profile shown in FIG. 15A. In the first step (S101) and the second step (S102), the LCO particles on the resin substrate do not change because they are at room temperature and in an air atmosphere (or an inert atmosphere). On the other hand, in the third step (S103), the substrate is heated by a sintering treatment device (air atmosphere). Here, when the temperature exceeds the melting point of the resin substrate and the substrate is sufficiently heated, the weight of the substrate starts to decrease.

[0183] Figure 16 shows the results of thermogravimetry (TG) of the resin substrate. Weight loss begins at approximately 300°C, which exceeds the melting point of the resin substrate (approximately 260°C). FIG. 17 shows the results of thermogravimetry-mass spectrometry (TG-MS). FIG. 17A shows the measurement results of a mixed sample of LCO particles and a resin substrate. FIG. 17B shows the measurement results of a sample that was measured using only a resin substrate. From around 300°C, where the weight of the resin substrate begins to decrease, an increase in molecules with a molecular weight of 28 that are believed to be carbon monoxide (CO), a reducing gas, is confirmed. In FIG. 17B, CO shows an increasing tendency up to around 500°C (solid line in FIG. 17B), whereas in FIG. 17A, CO shows a decreasing tendency just before 400°C (solid line in FIG. 17A). In addition, around 500°C in FIG. 17A, a decrease in molecules with a molecular weight of 32 that are believed to be oxygen (broken line in FIG. 17A) was confirmed, and an increase in molecules with a molecular weight of 44 that are believed to be carbon dioxide (dotted line in FIG. 17A) was confirmed. From the results of TG and TG-MS, the following is inferred.

[0184] As the temperature rises, the weight of the resin substrate starts to decrease (around 300°C), and the reducing gas CO is generated, increasing the reducing ability. Some of the generated CO contributes to the reduction of the LCO particles. As a result, the LCO particles are reduced and decomposed, and are thought to change into particles P1r that have some voids inside the LCO particles (Figure 15B). On the other hand, the amount of CO generated decreases as the base material decreases, so reductive decomposition gradually becomes more difficult to occur. As the weight of the base material decreases, the effect of CO decreases, and oxidation becomes dominant over reduction for the LCO particles. The reduced particles P1r are oxidized again to LiCoO2, which is trivalent Co (around 500°C). At this point, it is believed that the LCO particles change to have a core portion P1a, a shell portion P1b, and protrusions P1c protruding radially from the surface of the shell portion, while retaining the gaps P1d generated during reductive decomposition inside the LCO particles. 18-2A to 18-2D show the results of STEM-EELS (FIGS. 18-2A to 18-2D) at the respective sites shown in FIGS. 18-2A to 18-2D in the LCO particle (FIG. 18-1) after the third step. It can be seen that the core portion P1a (Area 4 in FIG. 18-2D), the shell portion P1b (Area 2 in FIG. 18-2B), and the protruding portion P1c (Area 1 in FIG. 18-2A) in the LCO particle contain Co and are oxides having almost the same composition.

[0185] (4th step) The fourth step is a step of post-treating the three-dimensional object obtained in the third step. By carrying out the post-treatment, it becomes easier to fill the electrode precursor with the filler material in the filling step (step 2-1) described later. Examples of post-treatment include the pressurizing step described below, as well as physical and chemical treatments for improving wettability and filling properties, and known treatment methods can be used. Specifically, examples of physical treatment include physical treatment of a three-dimensional object by laser edging, etc. Examples of other post-treatments include surface modification by UV irradiation or corona discharge, and chemical treatments such as gas adsorption. The pressurizing step will be described below as an example.

[0186] For example, the fourth step is a step of pressurizing the three-dimensional object 16 obtained in the third step from which the resin base material has been removed (FIG. 12). The three-dimensional object 16 may be pressurized by a pressurizing means 422 during cooling or heat dissipation after heating. Alternatively, after the resin base material has been removed by a sintering treatment device, the object may be pressurized by a separate pressurizing device. The pressurizing method is not particularly limited, but is preferably performed by, for example, vacuum degassing, isostatic pressing, a general hydraulic press machine, a roller press machine, or the like. Among these, it is preferable to perform pressing by combining vacuum degassing and isostatic pressing. It is also preferable to perform the fourth step by laminating the three-dimensional object with a release material such as nichrome foil, and more preferably to further pack the object in a laminate film. The pressure applied during pressurization is preferably 5 to 500 MPa. By applying pressure, the size of the pores (voids) in the three-dimensional object from which the resin base material has been removed decreases. This is generally known as the capillary phenomenon. As shown in Fig. 1, as the pore size decreases, the liquid becomes more easily permeable. Therefore, by performing the post-treatment by pressurization, the filling property of the filling material during the filling process of the filling material described below is further improved. In addition, by performing the post-treatment by pressurization, the particles constituting the three-dimensional object can be easily contacted with each other. As a result, the ionic conductivity and electronic conductivity can be increased, and the strength of the three-dimensional object can be increased. After the fourth step, another heat treatment may be performed to increase the density and strength of the three-dimensional object. In this case, the sintering treatment device of the third step may be used, or sintering may be performed using a separate electric furnace, tubular furnace, hot press, hot isostatic pressing device (HIP), etc.

[0187] The electrode precursor obtained through the first to fourth steps includes active material particles and electrolyte particles, and has voids. The voids refer to, for example, gaps between the active material particles and the electrolyte particles. By having the voids, it is possible to fill the electrode precursor with a filling material, as described below. The proportion of the voids in the electrode precursor may be 1 to 30% by volume, or 5 to 20% by volume. If there are few voids, the electrode precursor is difficult to be filled with the filler material in the filling process of the filler material described later, and the effect of the filler material is difficult to be expressed. On the other hand, if there are many voids, the contact between the active material particles and the electrolyte particles may be insufficient, and the ionic conductivity and electronic conductivity in the electrode may decrease. The ratio of voids can be determined by so-called 3D-SEM, in which continuous cross-sectional images are obtained by repeating cross-sectional processing (FIB) and SEM observation, and a three-dimensional image is obtained by reconstructing the images using analysis software. For a region of □50 μm×50 μm of the electrode part, cross-sectional processing and SEM observation are repeated every 0.1 μm in the stacking direction to obtain a three-dimensional image of 50 μm×50 μm×10 μm, and the ratio of voids is calculated. The ratio of voids may also be determined from a BIB-SEM image of a two-dimensional positive electrode cross section. At this time, an SEM image of a 500 μm×10 μm region including the center of the positive electrode cross section may be obtained, and the ratio of voids may be calculated. It can be calculated as the ratio of voids (pixels) to the entire image (pixels) using commercially available image analysis software (Photoshop (registered trademark)).

[0188] <Electrode manufacturing method> An example of a method for producing an electrode will be described in detail below with reference to the drawings. The electrode can be made into a positive electrode by using a positive electrode precursor as the electrode precursor. Also, the electrode can be made into a negative electrode by using a negative electrode precursor as the electrode precursor.

[0189] The method for producing an electrode according to the present disclosure includes the following four steps (step 1-1, step 2-1, step 3-1, and step 4-1). It may also include step 5-1. The order of steps 1-1 and 2-1 is not particularly limited, and step 2-1 may be performed after step 1-1, or step 1-1 may be performed after step 2-1. FIG. 19 is a conceptual diagram showing a method for manufacturing an electrode. (1) Step 1-1 (not shown) of preparing an electrode precursor containing active material particles and having voids between the active material particles (2) Step 2-1 (S201 in FIG. 19) of preparing a filling material to be filled into the electrode precursor; (3) Step 3-1 (S202 in FIG. 19) of filling the filling material from the outside to the inside of the electrode precursor; (4) Step 4-1 (S203 in FIG. 19 ) of retaining the filling material filled in the electrode precursor inside the electrode precursor (5) Step 5-1 (S204 in FIG. 19) of post-treating the electrode precursor obtained by step 4-1

[0190] (Step 1-1) Step 1-1 is a step of preparing an electrode precursor that contains active material particles and has voids between the active material particles. Step 1-1 is not particularly limited as long as the electrode precursor can be prepared, but the electrode precursor can be prepared, for example, by using the above-mentioned method for producing an electrode precursor. That is, step 1-1 preferably includes a first step of forming a particle layer containing active material particles and electrolyte particles on a resin substrate having an adhesive portion, a second step of forming a laminate by stacking a plurality of resin substrates on which the particle layer is formed, a third step of removing the resin substrate from the laminate to form a three-dimensional object containing the active material particles and the electrolyte particles, and a fourth step of post-treating the three-dimensional object.

[0191] (Step 2-1) Step 2-1 is a step of preparing a filling material to be filled into the electrode precursor. Step 2-1 includes a step of blending and preparing the following raw materials. As described above, the filling material needs to be liquid in order to fill the voids in the electrode precursor. As the filling material, for example, a solution in which at least one selected from the group consisting of a conductive resin and a precursor of a conductive resin is dissolved in a solvent may be used, or a dispersion in which at least one selected from the group consisting of a conductive resin and a precursor of a conductive resin is dispersed in a dispersion medium may be used. As the precursor of the resin having electrical conductivity, for example, a monomer, oligomer, or polymer of a thermosetting resin or a photocurable resin can be used as the precursor of the resin having electrical conductivity. That is, the resin having electrical conductivity is preferably a cured product of a precursor of the resin having electrical conductivity. Specific examples of the precursor of the resin having electrical conductivity include an ionic compound having a structure corresponding to the structure shown in the above formulas (1) to (6), the above polyol, and the above isocyanate compound.

[0192] The filling material may be, for example, a mixture of the following ingredients: At least one selected from the group consisting of a resin having electrical conductivity and a precursor of a resin having electrical conductivity Supporting electrolyte such as lithium salt if necessary Solvent or dispersion medium Conductive additives as required

[0193] The solvent or dispersion medium is not particularly limited, and for example, an organic solvent can be used. As the organic solvent, for example, alcohols such as methanol and ethanol, ketones such as methyl ethyl ketone, acetone, and acetylacetone, and hydrocarbon solvents such as hexane and cyclohexane can be used. Among them, methyl ethyl ketone is preferable.

[0194] The filling material may contain a supporting electrolyte. When the filling material contains a supporting electrolyte, the resin having electrical conductivity in the electrode can contain the supporting electrolyte. In addition, the above-mentioned supporting electrolyte and the conductive assistant can be used.

[0195] (Step 3-1) Step 3-1 is a step of filling the electrode precursor from the outside to the inside with the filling material prepared in step 2-1. The filling means can be a known means for filling a liquid. The filling means preferably includes, for example, a coating step of coating the electrode precursor with the filling material and a penetration step of penetrating the coated filling material into the inside of the electrode precursor. It is more preferable to include a penetration step of penetrating the filling material into the inside of the electrode precursor so as to contact the inner surface of the active material particles, or a penetration step of penetrating the filling material into the inside of the electrode precursor so as to contact the outer surface of the active material particles. Examples of devices used in the coating step include an inkjet device, a dispenser device, a dip coating device, a spin coating device, a spray coating device, and a roll coating device. Among them, it is preferable to use a dispenser device. Examples of devices used in the penetrating step include a vacuum dryer and a vacuum packaging machine. In addition, pressure may be applied with a weight or the like to support the penetration.

[0196] 20A is a schematic diagram showing the state of filling by a dispenser device 511. Filling material 50 is contained in a syringe in the dispenser device 511, and is applied to electrode precursor 18 through a nozzle at the tip of the syringe. Meanwhile, electrode precursor 18 formed on substrate 14 (electrode current collector or solid electrolyte sheet) is fixed to a support table 512. Here, the filling material may be applied to a surface 18-1 (hereinafter also referred to as a particle arrangement surface) opposite to a contact surface 18-2 (hereinafter also referred to as a substrate support surface) of the electrode precursor 18 that contacts the substrate 14, or to an end portion 17 of the electrode precursor 18, but it is preferable to apply the filling material to the end portion 17. The reason for this will be described later. The end portion refers to the xz and yz surfaces when the substrate surface of the electrode precursor is the xy surface and the lamination direction is the z direction ( FIG. 13B ). In the third step, the electrode precursor 18 is formed into a three-dimensional object by removing the resin base material from the laminate, so that the electrode precursor 18 has pores that communicate from the particle arrangement surface 18-1. Also, pores that communicate from the end portion 17 are provided. This makes it easier for the filling material 50 to evenly permeate the entire electrode precursor 18. As a result, the conductive resin is more likely to be positioned so as to contact the inner surface of the active material particles. Also, the conductive resin is more likely to be positioned so as to contact the outer surface of the active material particles and connect the active material particles. In addition, at the end portions, the interlayers of the laminated structure of the electrode precursor are exposed, so that when the filling material is applied to the end portions, the filling material is easily filled into the interior. On the other hand, when the filling material 50 is applied from the particle arrangement surface 18-1 of the electrode precursor 18, that is, from the xy plane, it is preferable to apply the filling material in small amounts to multiple locations on the xy plane in order to ensure uniform penetration.

[0197] 20B is a schematic diagram showing the filling process by a dip coating device 513. The filling material 50 is contained in a dipping container 514. As the dip coating device 513 moves in the direction of the arrow, the filling material 50 is applied to the end of the electrode precursor 18.

[0198] 20C is a schematic diagram showing the state of filling by a spin coater 515. The filling material 50 is contained in a syringe in a dispenser device 511, and is applied onto the resin substrate 14 through a nozzle at the tip of the syringe. Meanwhile, the electrode precursor 18 formed on the resin substrate 14 (electrode current collector or solid electrolyte sheet) is fixed to a support table of the spin coater 515. The filling material 50 applied onto the resin substrate 14 is applied to the end of the electrode precursor 18 by the centrifugal force of the spin coater 515.

[0199] (Step 4-1) Step 4-1 is a step of retaining the filling material filled in the electrode precursor in step 3-1 in the electrode precursor. The means for retaining is not particularly limited and is appropriately selected depending on the filling material. For example, a step of thickening the filling material and a step of hardening the filling material can be mentioned. Specifically, when a thermosetting polymer electrolyte is used as the filling material, a known means such as a vacuum oven can be used. When a UV-curable polymer electrolyte is used as the filling material, a known means such as a UV irradiation device can be used. When using a UV irradiation device, depending on the thickness of the electrode, the filling material may not be easily cured by UV irradiation. In that case, the thickness of the electrode precursor is set to a thickness that allows the filled filling material to be easily cured, and multiple electrode precursors are molded on a substrate with high releasability, and after the filling material is cured in each electrode precursor, the electrodes are obtained by transfer lamination. In addition, the filling in the 3-1 step may be performed all at once, or may be performed in small amounts in several separate steps. Specifically, when the filling is performed in small amounts in several separate steps, the electrode may be obtained as follows. That is, after a small amount of filling in the 3-1 step is performed once, the filling material is held inside the electrode precursor in the 4-1 step. Thereafter, the filling in the 3-1 step is performed again, and the filling material is held inside the electrode precursor in the 4-1 step. In this way, the 3-1 step and the 4-1 step may be repeatedly performed to obtain the electrode precursor. The electrode precursor obtained in the step 4-1 can be used as an electrode. The electrode precursor obtained in the step 4-1 is preferably subjected to the step 5-1 to form an electrode.

[0200] (Step 5-1) Step 5-1 is a step of obtaining an electrode by post-treating the electrode precursor obtained in Step 4-1. Examples of post-treating include a pressurizing step of pressurizing the electrode precursor obtained in Step 4-1, a buffer layer forming step of forming an interface buffer layer with the electrolyte on the surface of the electrode, and a packaging step of vacuum packaging with a protective film or an AL laminate film to prevent peeling, cracking, and exposure to the air during transportation and storage. The pressurizing means used in the pressurizing step may be any known means, and specific examples thereof include vacuum degassing, isostatic pressurization, a general hydraulic press, and a roller press. Of these, it is preferable to use a combination of vacuum degassing and isostatic pressurization. The means in the buffer layer formation step can be a known coating means, specifically, vacuum deposition, ion plating, sputtering, chemical vapor deposition (CVD), and each coating means in step 3-1. A buffer layer sheet (such as a polymer electrolyte sheet) prepared separately may be laminated without using the above-mentioned means. Also, a buffer layer may be provided on the electrode by controlling the amount of filling material in step 3-1 in advance so that the filling material filled in step 3-1 also serves as a buffer layer.

[0201] <Secondary battery manufacturing method> A secondary battery can be manufactured by using the above-mentioned method for manufacturing an electrode. The method for manufacturing a secondary battery is not particularly limited, but the following specific examples can be mentioned. The above-mentioned electrode manufacturing method will be described in terms of the case where it is used as a manufacturing method for a positive electrode or a negative electrode. A positive electrode or a negative electrode, or both a positive electrode and a negative electrode, can be manufactured by the above-mentioned electrode manufacturing method using a current collector or an electrolyte formed by a separate means as a base.

[0202] The secondary battery can be manufactured by stacking the electrodes, the current collectors, and the electrolyte, packaging the stack with an aluminum laminate film or the like as necessary, and molding and pressing the stack. That is, the manufacturing method of the secondary battery may include a step of stacking the electrodes, the current collectors, and the electrolyte. The electrodes may be the above-mentioned electrodes. The method for producing a secondary battery may include a step of preparing an electrode by the above-mentioned electrode production method, and a step of providing a solid electrolyte adjacent to the electrode. The method may also include a step of providing the above-mentioned electrode and the solid electrolyte adjacent to the electrode together. That is, the electrode and the solid electrolyte may be prepared in separate steps, or may be prepared together in the same step.

[0203] Here, the other means for forming the electrolyte is a known means, for example, a means for forming electrolyte particles into pellets using a uniaxial pressurizing device or the like, and sintering the pellets in an electric furnace or the like. The manufactured components are stacked in the order of a positive electrode current collector, a positive electrode, an electrolyte, a negative electrode, and a negative electrode current collector to manufacture a secondary battery. Examples of the secondary battery include a laminated battery packed in a laminate film and a coin battery packed in a coin case. The particles constituting the positive electrode, electrolyte, and negative electrode may have different suitable temperatures and suitable atmospheres during sintering. When handling such materials, it is preferable to separately manufacture the positive electrode, electrolyte, and negative electrode, which are the respective components, and assemble them into a battery. In addition, when lithium metal or indium is used as the negative electrode, it is preferable to use the negative electrode as a metal foil or to form it into a current collector or electrolyte by a vacuum process such as sputtering. Since lithium metal has a strong reducing power, it is easily decomposed depending on the type of solid electrolyte. In that case, a buffer layer may be provided between the electrode and the electrolyte. As the buffer layer, it is preferable to use a polymer electrolyte or the like.

[0204] In a specific example of the method for producing the secondary battery, the electrode is produced by forming a laminate of a positive electrode or a negative electrode on a current collector or an electrolyte as a base using the above-mentioned electrode production method. On the other hand, a laminate including two or more selected from the group consisting of a positive electrode current collector, a positive electrode, an electrolyte, a negative electrode, and a negative electrode current collector, which are the main components of a secondary battery, can be molded to produce a three-dimensional object including an electrode. For example, each of the substrates is prepared by the particle arrangement device 1. That is, a positive electrode current collector substrate, a positive electrode substrate, an electrolyte substrate, a negative electrode substrate, and a negative electrode current collector substrate. Each substrate may contain a plurality of types of particles (for example, positive electrode active material particles and electrolyte particles in the case of a positive electrode substrate), or may contain only a single type of particle. When only a single type of particle is contained, a single type of dense particle layer can be formed on the substrate by using the same type of filler in the filling devices 24a and 24b. The electrolyte base material is formed of a particle layer containing electrolyte particles. The negative electrode base material is formed of a particle layer containing negative electrode active material particles. The current collector base material is formed of a particle layer containing conductive particles. These base materials are laminated in the order of positive electrode current collector base material, positive electrode base material, electrolyte base material, negative electrode base material, and negative electrode current collector base material using a laminate molding device to produce a laminate, and a three-dimensional object containing an electrode is formed using a sintering treatment device to obtain a secondary battery precursor containing an electrode precursor. The electrode precursor is filled and retained with a filling material (steps 2-1 to 4-1), to produce a secondary battery. Furthermore, a bipolar secondary battery can be manufactured in the same manner, in which a positive electrode and a negative electrode are laminated on both sides of a current collector substrate. In this case, the filling material is filled and held at least in the electrodes, but it may be filled and held in the electrolyte or current collector other than the electrodes.

[0205] <Electrode complex> The electrode composite includes the electrode of the present disclosure and an electrolyte layer that transfers active material between the electrode and the electrolyte layer. By providing an electrode that serves as a positive electrode or a negative electrode to the electrode composite, it is possible to provide a secondary battery that can reduce the expansion and contraction of the active material particles and suppress a decrease in battery output.

[0206] <Secondary battery> The secondary battery includes the positive electrode of the present disclosure and an electrolyte layer that transfers active material between the positive electrode and the electrolyte layer. The secondary battery also includes a negative electrode that transfers active material between the electrolyte layer and the negative electrode. Such a secondary battery can mitigate the expansion and contraction of active material particles and suppress a decrease in battery output. In addition, the secondary battery can be an all-solid-state battery by using a solid electrolyte such as an ion-conductive solid as the electrolyte layer. The method for producing the secondary battery is not particularly limited, but the above-mentioned production method can be used. EXAMPLES

[0207] The present disclosure will be described in more detail below using examples, but the present disclosure is not limited to these examples. In the following examples, unless otherwise specified, the number of parts is based on parts by mass.

[0208] Example 1 [Example of positive electrode manufacturing] <Production Example of Positive Electrode Precursor> The positive electrode precursor of Example 1 was formed by the above-mentioned method for producing an electrode precursor. First, using a particle arrangement device 1 shown in FIG. 2, a particle layer consisting of positive electrode active material particles (first particles P1) and electrolyte particles (second particles P2) was formed on a resin substrate having an adhesive portion to form a resin substrate (first step). The first particles P1 were LiCoO2 (hereinafter, LCO), and the second particles P2 were Li3BO3 (hereinafter, LBO). The LCO used was manufactured by Nippon Chemical Industry Co., Ltd. (Cellseed C-5H), and the LBO used was manufactured by Toshima Manufacturing Co., Ltd. The first base material 11a was a PDMS (ultraviolet-curable liquid silicone rubber) sheet having a concave-convex structure on its surface. The second base material 11b was a polyester (PET) sheet. A resin sheet having an adhesive portion coated with an acrylic adhesive material on both sides was used. The second base material 11b (PET) used had a thickness of 3 μm. The adhesive portion had a thickness of 1 μm. LCO particles were arranged in a honeycomb pattern on the resin sheet, and LBO particles were arranged in the areas where no LCO particles were arranged (FIG. 9B).

[0209] The second step was carried out using the resin substrate on which the particle layer was formed, obtained in the first step. That is, using the laminate forming apparatus U3 shown in Fig. 11, the resin substrate on which the particle layer was formed was laminated (three layers) on the current collector AC-1 (Al foil) to form a laminate. Thereafter, the resin base material was removed from the laminate by heating using a sintering treatment device U4 shown in Fig. 12 to form a three-dimensional object (third process). The sintering atmosphere was air, the sintering temperature was 510°C, and the sintering time was 1 hour. The three-dimensional object was laminated with a release material (nichrome foil), packed in a laminate film (Co-pack), and vacuum-packed using a vacuum packaging machine. The vacuum-packed laminate film was pressurized (196 MPa) for 1 minute using an isostatic pressure device to obtain a positive electrode precursor (fourth step).

[0210] <Preparation example of filling material (step 2-1)> (Production Example of Ionic Compound I-01) In a recovery flask equipped with a Dimroth condenser, add a stirrer and tetrahydrofuran (THF 60 ml of bis(trifluoromethanesulfonyl)imide (manufactured by Kanto Chemical Co., Ltd.) was added, and 24.0 g (0.60 mol) of sodium hydride (60 mass%, dispersed in liquid paraffin, manufactured by Tokyo Chemical Industry Co., Ltd.) was dispersed, and the eggplant flask was cooled in an ice bath. A solution of 10.2 g (0.15 mol) of imidazole (manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in 60 ml of THF was slowly dropped, and the ice bath was removed and stirred at room temperature for 2 hours. 47.6 g (0.38 mol) of 2-bromoethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) was added at room temperature, and the mixture was heated and refluxed at 70°C for 7 hours. The reaction solution after the reaction was filtered, the insoluble matter was washed away with THF, and the solvent of the obtained filtrate was distilled off under reduced pressure. The obtained product was dissolved in 200 ml of dichloromethane, and an aqueous solution of 43.6 g (0.15 mol) of bis(trifluoromethanesulfonyl)imide lithium (manufactured by Tokyo Chemical Industry Co., Ltd.) was added as an anion raw material, and the mixture was stirred at room temperature for 10 hours. The obtained solution was separated to obtain an organic layer. This organic layer was washed three times with pure water. Next, dichloromethane was distilled off under reduced pressure to obtain ionic compound I-01. Ionic compound I-01 is a compound represented by the following formula. [ka]

[0211] (Example of manufacturing a conductive resin precursor) In a nitrogen atmosphere, 19.6 parts by mass of polymeric MDI (trade name: Millionate MR-200, manufactured by Tosoh Corporation) as an isocyanate was slowly dropped into a reaction vessel, while the temperature in the reaction vessel was kept at 65°C, and 120.5 parts by mass of polyether polyol (trade name: Adeka Polyol PR-5007, manufactured by ADEKA Corporation) was gradually dropped. After the dropwise addition was completed, the mixture was reacted at a temperature of 65°C for 3.5 hours. The resulting reaction mixture was cooled to room temperature, and 49.8 parts by mass of methyl ethyl ketone was added to obtain a solution of an isocyanate-terminated prepolymer having an isocyanate group content of 2.5% by mass.

[0212] The following materials were mixed with 100 parts by mass of the obtained solution of isocyanate-terminated prepolymer and stirred to obtain a filling material. Adeka Polyol PR-5007 113 parts by weight Ionic compound I-1 3.7 parts by mass Supporting electrolyte (lithium bis(trifluoromethanesulfonyl)imide (Tokyo Chemical Industry Co., Ltd.)) 18.6 parts by mass Methyl ethyl ketone 175 parts by weight

[0213] Next, the positive electrode precursor obtained in the fourth step was filled with the prepared filling material from a part of the end face located on the periphery of the positive electrode precursor using the application device shown in FIG. 20A (step 3-1). The positive electrode precursor filled with the filling material was heated in a vacuum oven (140°C) for 1 hour to harden the filling material into a conductive resin, and the positive electrode A-1 was formed (step 4-1). Samples with varying filling amounts of the filling material were prepared, and the level at which the conductive resin in the electrode penetrated without excess or deficiency was determined using the BIB-SEM described above.

[0214] A secondary battery was produced using the molded positive electrode A-1. The production method will be described. Other than the positive electrode A-1, the electrolyte layer SE-1 and the negative electrode C-1 were prepared by the following method. The electrolyte layer SE-1 was Li 1.5 Al 0.5 Ge 1.5 P3O 12The electrolyte sheet (thickness 260 μm) was prepared by pelletizing LAGP powder (manufactured by Toshima Manufacturing Co., Ltd.) with a uniaxial press and sintering it in an electric furnace (850 ° C / 12 h). The negative electrode C-1 was made of indium foil (thickness 50 μm, manufactured by Nilaco). The positive electrode current collector AC-1 (Al foil thickness 20 μm), the positive electrode A-1, the electrolyte layer SE-1, the negative electrode C-1, and the negative electrode current collector CC-1 (Cu foil thickness 20 μm) were laminated in this order, and the tab lead for the extraction electrode, which had been welded to the current collector in advance, was packed in an aluminum laminate film so that it was positioned outside the laminate. After that, it was formed into a laminate cell type using a vacuum packaging machine, and pressurized (196 MPa) for 1 minute using an isostatic pressure pressurizer to produce the secondary battery SB-1.

[0215] 22A to 22D are electron microscope images of the cross section of the positive electrode A-1 taken by a method described later. FIG. 22A is an electron microscope image. FIG. 22B identifies LCO particles (P1t, P1u, P1v, P1w, P1x, P1y, P1z) based on an EDX image (element Co), and shows the boundaries of the particles with dashed lines. The LCO particle has a core portion P1a, a shell portion P1b, and a protruding portion P1c protruding radially from the surface of the shell portion. In addition, a gap portion P1d exists between the core portion and the shell portion (FIG. 14). In FIG. 22B, the boundaries of the gap portions P1d in the particles P1t and P1u are shown with solid lines. In other words, it can be said that the solid lines represent the inner surfaces of the active material particles. Fig. 22C is an EDX image of sulfur element derived from the conductive resin. As in Fig. 22B, the boundaries of the particles are indicated by dashed lines. The conductive resin is present so as to contact the inner surfaces of the gaps P1d, i.e., the inner surfaces of the active material particles. The conductive resin is also arranged so as to contact the outer surfaces of the LCO particles and connect the LCO particles. Fig. 22D is an EDX image of boron element derived from the solid electrolyte LBO. As in Fig. 22B, the boundaries of the particles are indicated by dashed lines. As can be seen from Figs. 22C and 22D, the conductive resin and the inorganic electrolyte are unevenly distributed between the LCO particles.

[0216] FIG. 23 is a low-magnification electron microscope image of the cross section of the positive electrode A-1. FIG. 23A is an electron microscope image. FIG. 23B identifies LCO particles based on an EDX image (element Co), and particle boundaries are indicated by dashed lines. FIG. 23C is an EDX image (element Co), FIG. 23D is an EDX image (element C), and FIG. 23E is an EDX image (element B). In FIGS. 23C to 23E, the boundaries of the LCO particles are indicated by dashed lines. A conductive resin is present so as to contact the inner surface of the gap portion P1d, i.e., the inner surface of the active material particle. In addition, the conductive resin is arranged so as to contact the outer surface of the LCO particles and connect the LCO particles. Furthermore, the conductive resin is present in the LCO particles. It exists so as to overlap with the area containing BO.

[0217] Figures 24A to 24C are schematic diagrams showing features of the present disclosure, for example, according to Example 1. Figure 24A is a schematic diagram of an electrode, and Figure 24B shows the element distribution of EDX along line A-A' in Figure 24A. Figure 24C shows the element distribution of EDX along line B-B' in Figure 24A. 24A to 24C, the conductive resin is disposed in contact with the outer surfaces of the active material particles and connects the active material particles together, forming a good interface with the active material particles as well as with the supporting electrolyte particles, which is believed to improve ion diffusion within the electrode. It is also believed that the conductive resin changes shape in response to the expansion and contraction of the active material particles during charging and discharging, thereby suppressing the decrease in ionic conductivity and electronic conductivity. Furthermore, it is believed that the voids in the electrode function as spaces for deformation, including expansion and contraction of the conductive resin in response to the expansion and contraction of the active material particles.

[0218] The conductive resin is filled in the gaps P1d in the LCO particles. That is, it is located so as to be in contact with the inner surface of the LCO particles. In this way, the conductive resin forms a good interface with the LCO particle surface having the protrusions P1c, and also forms a good interface with the gaps P1d in the LCO particles, which is considered to further improve ion diffusion in the electrode. In addition, since the flexible conductive resin is filled in the LCO particles, the shape changes according to the expansion and contraction of the active material particles accompanying charging and discharging. As a result, it is considered that the decrease in ion conductivity and electronic conductivity in the particles is suppressed. Furthermore, it is considered that the conductive resin in contact with the inner and outer surfaces of the active material particles is deformed according to the expansion and contraction accompanying the charging and discharging of the active material particles so as to connect discontinuities (e.g., cracks and gaps) within the active material particles and discontinuities (e.g., voids) between the particles, thereby maintaining ion conductivity.

[0219] <Cross-section observation of positive electrode> To observe the cross section of the positive electrode, the battery was disassembled in the stacking direction to separate it and the positive electrode was removed. The removed positive electrode was cut with a wire saw (DWS3400 / wire diameter 170 μm, diamond diameter 30 μm). The cut surface was cross-sectionally processed with a broad ion beam of Ar (JEOL SM-09010 Cross Section Polisher). The cross-sectional processing conditions were a voltage of 6 kV and a current of 150 to 200 mA. The cross-section was photographed using an electron microscope (ULTRA55) to obtain a BIB-SEM image. The conditions were as follows: Detector: ESB (backscattered electron beam) Observation conditions: Accelerating voltage 3 kV Magnification: 1000x Filter: ESB filter biased to 1500V

[0220] Next, element mapping was obtained by SEM-EDX (XFlash Detector 630M manufactured by Bruker Corp.) From the element mapping results, the active material particles, electrolyte particles, and conductive resin were identified.

[0221] The evaluation method of the secondary battery will be described below. <Charge / discharge characteristics capacity retention rate> The mass M (g / cm) of active material particles per unit area of ​​the resin substrate on which the particle layer is formed 2 ) to calculate the mass of the positive electrode active material particles (M × number of layers × positive electrode area cm 2 The mass M of the active material particles per unit area was calculated as follows. The weight of the first base material 11a was measured after the first particles P1 were filled by the first filling device 24a in the particle arrangement device 1. Next, the above-mentioned first particles P1 were transferred to the second base material 11b. After that, the weight of the first substrate 11a was measured. The difference was calculated to obtain the mass of the first particles P1 on the second substrate 11b. The mass of the first particles P1 was then divided by the area of ​​the second substrate 11b (the area of ​​the concave-convex region) to calculate the mass M of the active material particles per unit area.

[0222] Another calculation method is to use ICP emission spectroscopy. The active material particle mass per unit area M (g / cm) is calculated in advance by the above-mentioned method or the like. 2 Three levels of resin substrates on which particle layers with clearly defined Co content are formed are prepared. These resin substrates are dissolved by microwave acid decomposition (ETHOS PRO), and the acid decomposition solution is diluted with ultrapure water. Then, ICP-AES measurement (CIROS CCD) is performed to quantify the Co element. The active material particle mass per unit area M (g / cm) for the obtained element concentration is 2 From the calibration curve, the active material particle mass M (g / cm) per unit area of ​​the resin substrate on which the particle layer to be measured is formed can be obtained. 2 ) can be obtained.

[0223] The current value at a current rate of 0.4 C was determined, and charge / discharge measurements (constant current charge / constant current discharge) were performed at a current rate of 0.4 C. The measurements were performed using a charge / discharge device (manufactured by BioLogic). Figure 21 shows the measured charge / discharge curves. The vertical axis represents the battery cell voltage (V vs. Li / Li + ) and the horizontal axis indicates the battery cell capacity (mAh / g). The capacity is the capacity per mass of the positive electrode active material. The actual capacity of the LCO was 120mAh / g, and the cutoff voltage (vs. Li) was 4.2V (charge) / 2.6V (discharge). The capacity retention rate was the ratio of the discharge capacity to the charge capacity (discharge capacity / charge capacity x 100%). The above measurement was repeated five times, and the average value was calculated. A value of 80% or more was considered good.

[0224] <Cycle characteristics> A cycle evaluation (repeated charge / discharge measurement in constant current mode) was performed at a current rate of 0.4 C. The charge / discharge measurement was repeated until the capacity retention rate described above was 80% or less, and the number of times n was calculated. A value of 10 or more was considered good. As a result of the battery evaluation, the capacity retention rate was 100%, and the number of cycles n was 12. According to the above evaluation, when the charge / discharge characteristics and cycle characteristics were good, the battery was rated as A (Table 1).

[0225] Example 2 A positive electrode A-2 was produced in the same manner as in Example 1, except that the filling material was applied to the particle arrangement surface of the positive electrode precursor and filled into the positive electrode precursor. A secondary battery SB-2 was produced in the same manner as in Example 1, except that the positive electrode A-2 was used. When the cross section of the positive electrode A-2 was observed, the conductive resin was located so as to contact the inner surface of the gap, similar to the positive electrode A-1. Also, similar to the positive electrode A-1, the conductive resin was located so as to contact the outer surface of the LCO particles and connect the LCO particles. Furthermore, similar to the positive electrode A-1, the conductive resin was present so as to overlap the region containing LBO. Also, the conductive resin and the inorganic electrolyte were unevenly distributed between the LCO particles. Moreover, it was confirmed that the obtained secondary battery SB-2 had good capacity retention and cycle characteristics, similar to the secondary battery SB-1.

[0226] Example 3 A positive electrode A-3 was produced in the same manner as in Example 1, except that the sintering temperature in the third step was changed from 510° C. to 700° C. In addition, a secondary battery SB-3 was produced in the same manner as in Example 1, except that the positive electrode A-3 was used. 25A to 25C are electron microscope images of a cross section of the positive electrode A-3. FIG. 25A is an electron microscope image, FIG. 25B is an EDX image (element C), and FIG. 25C is an EDX image (element B). Perhaps due to the firing, the oxidation of the LCO particles progressed, and they returned to a form close to that of the raw LCO particles, with no gaps being observed. In the cross-sectional structure of the obtained positive electrode A-3, the conductive resin was arranged so as to contact the outer surface of the LCO particles and connect the LCO particles. Furthermore, similar to the positive electrode A-1, the conductive resin was present so as to overlap the region containing LBO. Furthermore, the conductive resin and the inorganic electrolyte were unevenly distributed between the LCO particles. Moreover, it was confirmed that the obtained secondary battery SB-3 had good capacity retention and cycle characteristics, similar to the secondary battery SB-1.

[0227] Example 4 A positive electrode A-4 was produced in the same manner as in Example 1, except that the first particles were changed to LCO (Cellseed C-8H) having a large particle size. When a cross-sectional observation of the positive electrode A-4 was performed, it was found that, like the positive electrode A-1, the conductive resin was located so as to contact the inner surface of the gap. Also, like the positive electrode A-1, the conductive resin was located so as to contact the outer surface of the LCO particles and connect the LCO particles. Furthermore, like the positive electrode A-1, the conductive resin was present so as to overlap the region containing LBO. Also, between the particles of the LCO particles, the conductive resin and the inorganic electrolyte were unevenly distributed together. Also, it was confirmed that the obtained secondary battery SB-4 had good capacity retention and cycle characteristics, like the secondary battery SB-1.

[0228] Example 5 A positive electrode A-5 was produced in the same manner as in Example 1, except that pressure (50 MPa) was applied by the pressure means 422 in the sintering treatment device U4. When a cross-section of the positive electrode A-5 was observed, it was found that the conductive resin was located so as to contact the inner surface of the gap, similar to the positive electrode A-1. Also, similar to the positive electrode A-1, the conductive resin was located so as to contact the outer surface of the LCO particles and connect the LCO particles. Furthermore, similar to the positive electrode A-1, the conductive resin was present so as to overlap the region containing LBO. Also, between the particles of the LCO particles, the conductive resin and the inorganic electrolyte were unevenly distributed together. Also, it was confirmed that the obtained secondary battery SB-5 had good capacity retention and cycle characteristics, similar to the secondary battery SB-1.

[0229] Example 6 Li as electrolyte particles 5.9 Yb 0.81 La 0.09 Zr 0.1 Except for using (BO3)3(LYbBO-1), a positive electrode A-6 was produced in the same manner as in Example 1. In addition, a secondary battery SB-6 was produced in the same manner as in Example 1, except for using the positive electrode A-6. When the cross section of the positive electrode A-6 was observed, the conductive resin was located so as to contact the inner surface of the gap, similar to the positive electrode A-1. Also, similar to the positive electrode A-1, the conductive resin was located so as to contact the outer surface of the LCO particles and connect the LCO particles. Furthermore, similar to the positive electrode A-1, the conductive resin was present so as to overlap the region containing LBO. Also, the conductive resin and the inorganic electrolyte were unevenly distributed between the LCO particles. Moreover, it was confirmed that the obtained secondary battery SB-6 had good capacity retention and cycle characteristics, similar to the secondary battery SB-1.

[0230] Table 1 shows a comparison table summarizing the formulations and production conditions of Examples 1 to 6 and the evaluation results. [Table 1] In the table, the application location indicates the location where the filler material was applied to the positive electrode precursor in step 3-1, the contact location indicates the contact location between the conductive resin and the LCO particles, and the presence or absence of co-distribution indicates whether the conductive resin and the inorganic electrolyte are co-distributed unevenly.

[0231] The present disclosure relates to the following configurations and methods. [Configuration 1] An electrode for use in a secondary battery, The electrode includes active material particles and a conductive resin, the active material particles having an inner surface; The conductive resin is positioned so as to be in contact with the inner surface. [Configuration 2] The electrode according to configuration 1, wherein the conductive resin includes an ionic conductive resin. 3. The electrode according to claim 1 or 2, wherein the conductive resin comprises a resin having an ionic functional group and a supporting electrolyte. [Configuration 4] 4. The electrode according to any one of configurations 1 to 3, wherein the conductive resin contains a urethane resin having an ionic functional group and a supporting electrolyte. [Configuration 5] 5. The electrode according to any one of configurations 1 to 4, wherein the inner surface is continuous with the outer surface of the active material particle. [Configuration 6] 6. The electrode according to claim 5, wherein the conductive resin is in contact with the outer surface. [Configuration 7] The electrode according to any one of configurations 1 to 6, wherein at least one selected from the group consisting of a conductive resin, a conductive assistant, and a supporting electrolyte is present between the active material particles. [Configuration 8] A supporting electrolyte is contained between the active material particles, 8. The electrode according to any one of aspects 1 to 7, wherein the supporting electrolyte comprises an inorganic electrolyte. [Configuration 9] 9. The electrode of claim 8, wherein between the particles, a region containing the conductive resin overlaps a region containing the inorganic electrolyte. [Configuration 10] 10. The electrode according to any one of aspects 1 to 9, wherein the active material particles contain lithium cobalt oxide. [Configuration 11] 11. The electrode according to any one of configurations 5 to 10, wherein the active material particles have protrusions protruding from the outer surface. [Configuration 12] 12. The electrode according to any one of configurations 1 to 11, wherein the conductive resin contains at least one of polyurethane, polyacrylic, and polyether in its main chain structure. [Configuration 13] The electrode according to any one of configurations 1 to 12, wherein the conductive resin contains a polyether, which is a copolymer of polyethylene glycol and polypropylene glycol, in the main chain structure. [Configuration 14] 14. The electrode according to any one of configurations 1 to 13, wherein the conductive resin has higher flexibility than the active material particles. [Configuration 15] An electrode for use in a secondary battery, The electrode includes active material particles and a conductive resin, the active material particles have an outer surface; The resin is disposed so as to be in contact with the outer surface and to connect the active material particles. [Configuration 16] 16. The electrode of claim 15, wherein the conductive resin comprises an ionic conductive resin. [Configuration 17] 17. The electrode according to embodiment 15 or 16, wherein the conductive resin contains at least one of polyurethane, polyacrylic, and polyether in its main chain structure. [Configuration 18] 18. The electrode according to any one of configurations 15 to 17, wherein the conductive resin contains polyether, which is a copolymer of polyethylene glycol and polypropylene glycol, in its main chain structure. [Configuration 19] the active material particles having an inner surface; 19. The electrode according to any one of aspects 15 to 18, wherein the inner surface is continuous with the outer surface. [Configuration 20] 20. The electrode of claim 19, wherein the conductive resin is positioned so as to contact the inner surface. [Configuration 21] A supporting electrolyte is contained between the active material particles, 21. The electrode according to any one of aspects 15 to 20, wherein the supporting electrolyte comprises an inorganic electrolyte. [Configuration 22] 22. The electrode of claim 21, wherein between the particles, a region containing the conductive resin overlaps a region containing the inorganic electrolyte. [Configuration 23] An electrode composite including an electrode and an electrolyte layer that transfers an active material between the electrode and the electrolyte layer, 23. An electrode composite, wherein the electrode is the electrode according to any one of configurations 1 to 22. [Configuration 24] A secondary battery including a positive electrode and an electrolyte layer that transfers an active material between the positive electrode and the electrolyte layer, The positive electrode is the electrode according to any one of configurations 1 to 22, The secondary battery includes a negative electrode that transfers the active material between the negative electrode and the electrolyte layer. [Method 25] A 1-1 step of preparing an electrode precursor including active material particles and having gaps between the active material particles; A 2-1 step of preparing a filling material to be filled into the electrode precursor; A 3-1 step of filling the filling material from the outside to the inside of the electrode precursor; and a 4-1 step of retaining the filling material filled inside the electrode precursor inside the electrode precursor. [Method 26] 26. The method for producing an electrode according to Method 25, wherein the step 3-1 includes a penetration step of penetrating the filler material into the inside of the electrode precursor so as to be in contact with the outer surfaces of the active material particles. [Method 27] 27. The method for producing an electrode according to Method 25 or 26, wherein Step 1-1 includes a step of forming an inner surface on the active material particles. [Method 28] 28. The method of claim 27, wherein the step of forming an inner surface on the active material particles is a step of sintering the active material particles. [Method 29] The step 1-1 is A first step of forming a particle layer including active material particles and electrolyte particles on a resin substrate having an adhesive portion; a second step of forming a laminate by laminating a plurality of the resin substrates on which the particle layers are formed; a third step of removing the resin substrate from the laminate to form a three-dimensional object including active material particles and electrolyte particles; A fourth step of post-treating the three-dimensional object; 29. A method for producing an electrode according to any one of Methods 25 to 28, comprising: [Method 30] 30. The method for producing an electrode according to any one of Methods 25 to 29, wherein the step 3-1 includes a penetration step of penetrating the filler material into the inside of the electrode precursor so as to be in contact with the inner surfaces of the active material particles. [Method 31] The electrode precursor has an end portion, 31. The method for producing an electrode according to any one of Methods 25 to 30, wherein the step 3-1 includes a step of applying the filling material to the end of the electrode precursor.

Claims

1. An electrode for use in a secondary battery, The electrode includes active material particles and a conductive resin, the active material particles having an inner surface; The conductive resin is positioned so as to be in contact with the inner surface.

2. The electrode according to claim 1 , wherein the conductive resin includes an ionic conductive resin.

3. The electrode according to claim 1 , wherein the conductive resin comprises a resin containing an ionic functional group and a supporting electrolyte.

4. 2. The electrode according to claim 1, wherein the conductive resin comprises a urethane resin containing an ionic functional group and a supporting electrolyte.

5. The electrode according to claim 1 , wherein the inner surface is continuous with the outer surface of the active material particles.

6. The electrode according to claim 5 , wherein the conductive resin is in contact with the outer surface.

7. The electrode according to claim 1 , further comprising at least one selected from the group consisting of a conductive resin, a conductive assistant, and a supporting electrolyte, between the active material particles.

8. A supporting electrolyte is contained between the active material particles, 10. The electrode of claim 1, wherein the supporting electrolyte comprises an inorganic electrolyte.

9. The electrode according to claim 8 , wherein a region between the particles containing the conductive resin overlaps a region between the particles containing the inorganic electrolyte.

10. 10. The electrode of claim 1, wherein the active material particles comprise lithium cobalt oxide.

11. The electrode according to claim 5 , wherein the active material particles have protrusions protruding from the outer surface.

12. 2. The electrode according to claim 1, wherein the conductive resin contains at least one of polyurethane, polyacrylic, and polyether in its main chain structure.

13. 2. The electrode according to claim 1, wherein the conductive resin contains polyether, which is a copolymer of polyethylene glycol and polypropylene glycol, in its main chain structure.

14. The electrode according to claim 1 , wherein the conductive resin has a higher flexibility than the active material particles.

15. An electrode for use in a secondary battery, The electrode includes active material particles and a conductive resin, the active material particles have an outer surface; The resin is disposed so as to be in contact with the outer surface and to connect the active material particles.

16. The electrode according to claim 15 , wherein the conductive resin comprises an ionic conductive resin.

17. 16. The electrode according to claim 15, wherein the conductive resin contains at least one of polyurethane, polyacrylic, and polyether in its main chain structure.

18. 16. The electrode according to claim 15, wherein the conductive resin contains polyether, which is a copolymer of polyethylene glycol and polypropylene glycol, in its main chain structure.

19. the active material particles having an inner surface; The electrode of claim 15 , wherein the inner surface is contiguous with the outer surface.

20. The electrode according to claim 19 , wherein the conductive resin is positioned so as to be in contact with the inner surface.

21. A supporting electrolyte is contained between the active material particles, 16. The electrode of claim 15, wherein the supporting electrolyte comprises an inorganic electrolyte.

22. 22. The electrode according to claim 21, wherein between the particles, a region containing the conductive resin overlaps a region containing the inorganic electrolyte.

23. An electrode composite including an electrode and an electrolyte layer that transfers an active material between the electrode and the electrolyte layer, An electrode composite, wherein the electrode is the electrode according to any one of claims 1 to 22.

24. A secondary battery including a positive electrode and an electrolyte layer that transfers an active material between the positive electrode and the electrolyte layer, The positive electrode is an electrode according to any one of claims 1 to 22, The secondary battery includes a negative electrode that transfers the active material between the negative electrode and the electrolyte layer.

25. A 1-1 step of preparing an electrode precursor including active material particles and having gaps between the active material particles; A 2-1 step of preparing a filling material to be filled into the electrode precursor; A 3-1 step of filling the filling material from the outside to the inside of the electrode precursor; and a 4-1 step of retaining the filling material filled inside the electrode precursor inside the electrode precursor.

26. The method for producing an electrode according to claim 25, wherein the 3-1 step includes a penetration step of penetrating the filler material into the inside of the electrode precursor so as to be in contact with outer surfaces of the active material particles.

27. The method for producing an electrode according to claim 25 or 26, wherein the 1-1 step includes a step of forming an inner surface on the active material particles.

28. The method for producing an electrode according to claim 27 , wherein the step of forming an inner surface on the active material particles is a step of sintering the active material particles.

29. The step 1-1 is A first step of forming a particle layer including active material particles and electrolyte particles on a resin substrate having an adhesive portion; a second step of forming a laminate by laminating a plurality of the resin substrates on which the particle layers are formed; a third step of removing the resin substrate from the laminate to form a three-dimensional object including active material particles and electrolyte particles; A fourth step of post-processing the three-dimensional object; A method for producing an electrode according to claim 25 or 26, comprising:

30. The method for producing an electrode according to claim 25 or 26, wherein the 3-1 step includes a penetration step of penetrating the filler material into the inside of the electrode precursor so as to be in contact with inner surfaces of the active material particles.

31. The electrode precursor has an end portion, The method for producing an electrode according to claim 25 or 26, wherein the 3-1 step includes a step of applying the filling material to the end portion of the electrode precursor.

Citation Information

Patent Citations

  • Battery and its manufacturing method

    JP2005268066A

  • Carbon material for nonaqueous secondary batteries, and lithium ion secondary battery

    JP2017027771A

  • Composite positive electrode active material for lithium secondary battery, manufacturing method for the same, and lithium secondary battery including positive electrode including the same

    JP2021141066A

  • Composite particles for lithium secondary battery positive electrodes, method for producing composite particles for lithium secondary battery positive electrodes, method for producing positive electrode for lithium secondary batteries, positive elect

    WO2012165422A1

  • Secondary battery

    WO2019093221A1